The Fourier transform and convolutions generated by a differential operator with boundary condition on a segment

Baltabek Kanguzhin and Niyaz Tokmagambetov

Department of Fundamental Mathematics,
Faculty of Mechanics and Mathematics,
Al–Farabi Kazakh National University, ave. Al–Farabi 71, 500040,
Almaty, Kazakhstan

E–mail: kanbalta@mail.ru, tokmagam@list.ru

Abstract. We introduce the concepts of the Fourier transform and convolution generated by an arbitrary restriction of the differentiation operator in the space L2(0,b).subscript𝐿20𝑏L_{2}(0,b). In contrast to the classical convolution, the introduced convolution explicitly depends on the boundary condition that defines the domain of the operator L.𝐿L. The convolution is closely connected to the inverse operator or to the resolvent. So, we first find a representation for the resolvent, and then introduce the required convolution.

keywords: fourier transform, convolution, differential operator, non–local boundary condition, resolvent, spectrum, coefficient functional, basis

MSC:AMS Mathematics Subject Classification (2000) numbers: 34B10, 34L10, 47G30, 47E05

0. Introduction

The standard Fourier transform is a unitary transform in the Hilbert space L2(,+)subscript𝐿2L_{2}(-\infty,\,+\infty) and it is generated by the operator of differentiation (iddx),𝑖𝑑𝑑𝑥(-i\frac{d}{dx}), because the system of exponents {exp(iλx),λR}𝑖𝜆𝑥𝜆𝑅\{\exp(i\lambda x),\,\lambda\in R\} is a system of "eigenfunctions"corresponding to its continuous spectrum. The Fourier transform is closely connected to the bilinear, commutative, associative convolution without annihilators. An important fact is that the convolution with the fundamental solution allows us to find solutions of the inhomogeneous differential equation, which commutes with differentiation. Corresponding constructions can be generalized to arbitrary self-adjoint operators. Instead of the differential operator (iddx)𝑖𝑑𝑑𝑥(-i\frac{d}{dx}) in the space L2(,+),subscript𝐿2L_{2}(-\infty,\,+\infty), consider an operator L𝐿L in the Hilbert space L2(0,b),subscript𝐿20𝑏L_{2}(0,b), where b<,𝑏b<\infty, which is generated by the differential operator (iddx)𝑖𝑑𝑑𝑥(-i\frac{d}{dx}) and a boundary condition. We introduce the concepts of the Fourier transform and convolution generated by an arbitrary restriction of the differentiation operator in the space L2(0,b).subscript𝐿20𝑏L_{2}(0,b). In contrast to the classical convolution, the introduced convolution explicitly depends on the boundary condition that defines the domain of the operator L.𝐿L.

As noted above, the convolution is closely connected to the inverse operator or to the resolvent. So, we first find a representation for the resolvent, and then introduce the required convolution.

1. Resolvent and spectrum of the operator L𝐿L

Without loss of generality, we assume that the origin belongs to the resolvent set of the operator L𝐿L, that is, there is an inverse operator L1.superscript𝐿1L^{-1}. By M. Otelbaev’s theorem [3] such operators are parameterized by a "boundary"function σ(x)𝜎𝑥\sigma(x) from the space L2(0,b).subscript𝐿20𝑏L_{2}(0,b).

Theorem 1.1 Let the action of the linear operator L𝐿L in L2(0,b)subscript𝐿20𝑏L_{2}(0,b) be defined by formula Ly=idydx𝐿𝑦𝑖𝑑𝑦𝑑𝑥Ly=-i\frac{dy}{dx} with some (fixed) boundary condition. Suppose there exists the inverse operator L1superscript𝐿1L^{-1} in L2(0,b).subscript𝐿20𝑏L_{2}(0,b). Then there is a unique function σ(x)L2(0,b)𝜎𝑥subscript𝐿20𝑏\sigma(x)\in L_{2}(0,b) such that the domain of operator L𝐿L is

D(L)={yW21[0,b]:y(0)0b(idydx)σ(x)¯𝑑x=0}.𝐷𝐿conditional-set𝑦subscriptsuperscript𝑊120𝑏𝑦0subscriptsuperscript𝑏0𝑖𝑑𝑦𝑑𝑥¯𝜎𝑥differential-d𝑥0D(L)=\{y\in W^{1}_{2}[0,b]:y(0)-\int^{b}_{0}(-i\frac{dy}{dx})\overline{\sigma(x)}dx=0\}.

Proof. Let us consider equation Ly=f,𝐿𝑦𝑓Ly=f, where fL2(0,b)𝑓subscript𝐿20𝑏f\in L_{2}(0,b). Since there is the bounded inverse operator L1superscript𝐿1L^{-1}. We have y=L1f𝑦superscript𝐿1𝑓y=L^{-1}f. Each solution of the differential equation idydx=f𝑖𝑑𝑦𝑑𝑥𝑓-i\frac{dy}{dx}=f has the form y=c+K1f𝑦𝑐superscript𝐾1𝑓y=c+K^{-1}f, where c𝑐c is an arbitrary constant and the operator K𝐾K corresponds to the Cauchy problem with zero condition at zero:

Ky=idydx,D(K)={yW21[0,b]:y(0)=0}.formulae-sequence𝐾𝑦𝑖𝑑𝑦𝑑𝑥𝐷𝐾conditional-set𝑦subscriptsuperscript𝑊120𝑏𝑦00Ky=-i\frac{dy}{dx},D(K)=\{y\in W^{1}_{2}[0,b]:y(0)=0\}.

Therefore, the constant c=L1fK1f𝑐superscript𝐿1𝑓superscript𝐾1𝑓c=L^{-1}f-K^{-1}f is dependent on f𝑓f and represents the value of a bounded linear functional on the Hilbert space L2(0,b)subscript𝐿20𝑏L_{2}(0,b). Then c=c(f),𝑐𝑐𝑓c=c(f), and by the Riesz theorem on bounded linear functionals on L2(0,b),subscript𝐿20𝑏L_{2}(0,b), we have

c=0bf(x)σ(x)¯𝑑x,σ(x)L2(0,b).formulae-sequence𝑐superscriptsubscript0𝑏𝑓𝑥¯𝜎𝑥differential-d𝑥𝜎𝑥subscript𝐿20𝑏c=\int_{0}^{b}f(x)\overline{\sigma(x)}dx,\sigma(x)\in L_{2}(0,b).

The element σ(x)𝜎𝑥\sigma(x) is uniquely determined. So, the solutions of the operator equation Ly=f𝐿𝑦𝑓Ly=f have the form y=0bf(x)σ(x)¯𝑑x+(K1f)(x).𝑦superscriptsubscript0𝑏𝑓𝑥¯𝜎𝑥differential-d𝑥superscript𝐾1𝑓𝑥y=\int_{0}^{b}f(x)\overline{\sigma(x)}dx+(K^{-1}f)(x). In the last equation, we substitute x=0𝑥0x=0. As a result, we get

y(0)=0bf(x)σ(x)¯𝑑x.𝑦0superscriptsubscript0𝑏𝑓𝑥¯𝜎𝑥differential-d𝑥y(0)=\int_{0}^{b}f(x)\overline{\sigma(x)}dx.

The converse assertion is also true and can be verified directly.

If the function y(x)𝑦𝑥y(x) from W21[0,b]subscriptsuperscript𝑊120𝑏W^{1}_{2}[0,b] satisfies condition

U(y)=0,𝑈𝑦0U(y)=0,

then it will belong to the domain DLsubscript𝐷𝐿D_{L} of L𝐿L, where

U(y):=y(0)0b(idydx)σ(x)¯𝑑x.assign𝑈𝑦𝑦0subscriptsuperscript𝑏0𝑖𝑑𝑦𝑑𝑥¯𝜎𝑥differential-d𝑥U(y):=y(0)-\int^{b}_{0}(-i\frac{dy}{dx})\overline{\sigma(x)}dx.

Let us denote by Δ(λ)Δ𝜆\Delta(\lambda) the entire function Δ(λ)=1λ0bexp(iλx)σ(x)¯𝑑x.Δ𝜆1𝜆subscriptsuperscript𝑏0𝑒𝑥𝑝𝑖𝜆𝑥¯𝜎𝑥differential-d𝑥\Delta(\lambda)=1-\lambda\int^{b}_{0}exp(i\lambda x)\overline{\sigma(x)}dx. Then the resolvent of the operator L𝐿L is

(LλI)1f=i0xexp(iλ(xξ))f(ξ)𝑑ξ+superscript𝐿𝜆𝐼1𝑓limit-from𝑖superscriptsubscript0𝑥𝑒𝑥𝑝𝑖𝜆𝑥𝜉𝑓𝜉differential-d𝜉(L-\lambda I)^{-1}f=i\int_{0}^{x}exp(i\lambda(x-\xi))f(\xi)d\xi+
+exp(iλx)Δ(λ)(0bf(x)σ(x)¯𝑑x+λi0bσ(x)¯𝑑x0xexp(iλ(xξ))f(ξ)𝑑ξ).𝑒𝑥𝑝𝑖𝜆𝑥Δ𝜆superscriptsubscript0𝑏𝑓𝑥¯𝜎𝑥differential-d𝑥𝜆𝑖superscriptsubscript0𝑏¯𝜎𝑥differential-d𝑥superscriptsubscript0𝑥𝑒𝑥𝑝𝑖𝜆𝑥𝜉𝑓𝜉differential-d𝜉+\frac{exp(i\lambda x)}{\Delta(\lambda)}(\int_{0}^{b}f(x)\overline{\sigma(x)}dx+\lambda i\int_{0}^{b}\overline{\sigma(x)}dx\int_{0}^{x}exp(i\lambda(x-\xi))f(\xi)d\xi). (1)

Indeed, denoting the right–hand side of this equality by y(x),𝑦𝑥y(x), we find it is a direct consequence of

y(x)=if(x)+iλy(x).superscript𝑦𝑥𝑖𝑓𝑥𝑖𝜆𝑦𝑥y^{\prime}(x)=if(x)+i\lambda y(x).

Let us calculate

U(y)=y(0)0b(idydx)σ(x)¯𝑑x=y(0)λ0by(x)σ(x)¯𝑑x0bf(x)σ(x)¯𝑑x=𝑈𝑦𝑦0subscriptsuperscript𝑏0𝑖𝑑𝑦𝑑𝑥¯𝜎𝑥differential-d𝑥𝑦0𝜆subscriptsuperscript𝑏0𝑦𝑥¯𝜎𝑥differential-d𝑥subscriptsuperscript𝑏0𝑓𝑥¯𝜎𝑥differential-d𝑥absentU(y)=y(0)-\int^{b}_{0}(-i\frac{dy}{dx})\overline{\sigma(x)}dx=y(0)-\lambda\int^{b}_{0}y(x)\overline{\sigma(x)}dx-\int^{b}_{0}f(x)\overline{\sigma(x)}dx=
=1Δ(λ)(0bf(x)σ(x)¯dx+λi0bσ(x)¯dx0xexp(iλ(xξ))f(ξ)dξ=\frac{1}{\Delta(\lambda)}(\int_{0}^{b}f(x)\overline{\sigma(x)}dx+\lambda i\int_{0}^{b}\overline{\sigma(x)}dx\int_{0}^{x}exp(i\lambda(x-\xi))f(\xi)d\xi-
λ0bσ(x)¯dx[i0xexp(iλ(xξ))f(ξ)dξ+-\lambda\int_{0}^{b}\overline{\sigma(x)}dx[i\int_{0}^{x}exp(i\lambda(x-\xi))f(\xi)d\xi+
+exp(iλx)Δ(λ)(0bf(x)σ(x)¯dx+λi0bσ(x)¯dx0xexp(iλ(xξ))f(ξ)dξ]0bf(x)σ(x)¯dx=+\frac{exp(i\lambda x)}{\Delta(\lambda)}(\int_{0}^{b}f(x)\overline{\sigma(x)}dx+\lambda i\int_{0}^{b}\overline{\sigma(x)}dx\int_{0}^{x}exp(i\lambda(x-\xi))f(\xi)d\xi]-\int^{b}_{0}f(x)\overline{\sigma(x)}dx=
=1Δ(λ)0bf(x)σ(x)¯𝑑x+iλΔ(λ)0bσ(x)¯𝑑x0xexp(iλ(xξ))f(ξ)𝑑ξabsent1Δ𝜆subscriptsuperscript𝑏0𝑓𝑥¯𝜎𝑥differential-d𝑥limit-from𝑖𝜆Δ𝜆subscriptsuperscript𝑏0¯𝜎𝑥differential-d𝑥superscriptsubscript0𝑥𝑒𝑥𝑝𝑖𝜆𝑥𝜉𝑓𝜉differential-d𝜉=\frac{1}{\Delta(\lambda)}\int^{b}_{0}f(x)\overline{\sigma(x)}dx+\frac{i\lambda}{\Delta(\lambda)}\int^{b}_{0}\overline{\sigma(x)}dx\int_{0}^{x}exp(i\lambda(x-\xi))f(\xi)d\xi-
iλΔ(λ)0bσ(x)¯𝑑x0xexp(iλ(xξ))f(ξ)𝑑ξ+limit-from𝑖𝜆Δ𝜆subscriptsuperscript𝑏0¯𝜎𝑥differential-d𝑥superscriptsubscript0𝑥𝑒𝑥𝑝𝑖𝜆𝑥𝜉𝑓𝜉differential-d𝜉-\frac{i\lambda}{\Delta(\lambda)}\int^{b}_{0}\overline{\sigma(x)}dx\int_{0}^{x}exp(i\lambda(x-\xi))f(\xi)d\xi+
+λ2i0bσ(x)¯𝑑x0xexp(iλ(xξ))f(ξ)𝑑ξ0bexp(iλμ)σ(μ)¯𝑑μlimit-fromsuperscript𝜆2𝑖subscriptsuperscript𝑏0¯𝜎𝑥differential-d𝑥superscriptsubscript0𝑥𝑒𝑥𝑝𝑖𝜆𝑥𝜉𝑓𝜉differential-d𝜉subscriptsuperscript𝑏0𝑒𝑥𝑝𝑖𝜆𝜇¯𝜎𝜇differential-d𝜇+\lambda^{2}i\int^{b}_{0}\overline{\sigma(x)}dx\int_{0}^{x}exp(i\lambda(x-\xi))f(\xi)d\xi\int^{b}_{0}exp(i\lambda\mu)\overline{\sigma(\mu)}d\mu-
λexp(iλx)Δ(λ)0bσ(x)¯𝑑x0xf(ξ)σ(ξ)¯𝑑ξlimit-from𝜆𝑒𝑥𝑝𝑖𝜆𝑥Δ𝜆superscriptsubscript0𝑏¯𝜎𝑥differential-d𝑥superscriptsubscript0𝑥𝑓𝜉¯𝜎𝜉differential-d𝜉-\lambda\frac{exp(i\lambda x)}{\Delta(\lambda)}\int_{0}^{b}\overline{\sigma(x)}dx\int_{0}^{x}f(\xi)\overline{\sigma(\xi)}d\xi-
λ2iexp(iλx)Δ(λ)0bσ(x)¯𝑑x0bσ(μ)¯𝑑μ0μexp(iλ(μξ))f(ξ)𝑑ξ1Δ(λ)0bf(x)σ(x)¯𝑑x+superscript𝜆2𝑖𝑒𝑥𝑝𝑖𝜆𝑥Δ𝜆superscriptsubscript0𝑏¯𝜎𝑥differential-d𝑥superscriptsubscript0𝑏¯𝜎𝜇differential-d𝜇superscriptsubscript0𝜇𝑒𝑥𝑝𝑖𝜆𝜇𝜉𝑓𝜉differential-d𝜉limit-from1Δ𝜆subscriptsuperscript𝑏0𝑓𝑥¯𝜎𝑥differential-d𝑥-\lambda^{2}i\frac{exp(i\lambda x)}{\Delta(\lambda)}\int_{0}^{b}\overline{\sigma(x)}dx\int_{0}^{b}\overline{\sigma(\mu)}d\mu\int_{0}^{\mu}exp(i\lambda(\mu-\xi))f(\xi)d\xi-\frac{1}{\Delta(\lambda)}\int^{b}_{0}f(x)\overline{\sigma(x)}dx+
+λΔ(λ)0bf(ξ)σ(ξ)¯𝑑ξ0bexp(iλx)σ(x)¯𝑑x=0.𝜆Δ𝜆subscriptsuperscript𝑏0𝑓𝜉¯𝜎𝜉differential-d𝜉subscriptsuperscript𝑏0𝑒𝑥𝑝𝑖𝜆𝑥¯𝜎𝑥differential-d𝑥0+\frac{\lambda}{\Delta(\lambda)}\int^{b}_{0}f(\xi)\overline{\sigma(\xi)}d\xi\int^{b}_{0}exp(i\lambda x)\overline{\sigma(x)}dx=0.

The proof is complete.

From the representation of the resolvent by definition of the spectrum of operator L𝐿L we get the following theorem.

Theorem 1.2 The set of zeros with multiplicities of the entire function Δ(λ)Δ𝜆\Delta(\lambda) is exactly the same as the spectrum of the operator L𝐿L.

Since Δ(λ)Δ𝜆\Delta(\lambda) is the entire function in λ𝜆\lambda, we have that the spectrum of the operator L𝐿L consists of isolated eigenvalues of finite multiplicity, and limit points of the spectrum can only be infinity. From the Paley – Wiener theorem it immediately follows that:

Theorem 1.3 The operator L𝐿L has either countable number of eigenvalues, or they are absent. The spectrum is empty if and only if there exists constant c[0,b]𝑐0𝑏c\in[0,b] such that σ(x)=i𝜎𝑥𝑖\sigma(x)=i for 0xc0𝑥𝑐0\leq x\leq c and σ(x)=0𝜎𝑥0\sigma(x)=0 for cxb.𝑐𝑥𝑏c\leq x\leq b.

The proof immediately follows from the representation

Δ(λ)=exp(iλc)0cexp(iλx)(σ(x)i)¯𝑑xλcbexp(iλx)σ(x)¯𝑑xΔ𝜆𝑒𝑥𝑝𝑖𝜆𝑐subscriptsuperscript𝑐0𝑒𝑥𝑝𝑖𝜆𝑥¯𝜎𝑥𝑖differential-d𝑥𝜆subscriptsuperscript𝑏𝑐𝑒𝑥𝑝𝑖𝜆𝑥¯𝜎𝑥differential-d𝑥\Delta(\lambda)=exp(i\lambda c)-\int^{c}_{0}exp(i\lambda x)\overline{(\sigma(x)-i)}dx-\lambda\int^{b}_{c}exp(i\lambda x)\overline{\sigma(x)}dx

and from the Paley–Wiener theorem, since the presence of the integral term in the right side of this equation leads to the existence of the growing product exp(iλc)Δ(λ)𝑒𝑥𝑝𝑖𝜆𝑐Δ𝜆exp(i\lambda c)\cdot\Delta(\lambda).

In what follows, suppose that the indicator diagram of the entire function Δ(λ)Δ𝜆\Delta(\lambda) is the segment [0,ib]0𝑖𝑏[0,ib]. Then the spectrum of the operator L𝐿L is a countable set.

In order for the indicator diagram Δ(λ)Δ𝜆\Delta(\lambda) to be represented by the interval [0,ib],0𝑖𝑏[0,ib], it is necessary and sufficient that

min(supp(σ(x)i))=0,max(supp(σ(x)))=b,formulae-sequence𝑠𝑢𝑝𝑝𝜎𝑥𝑖0𝑠𝑢𝑝𝑝𝜎𝑥𝑏\min(supp(\sigma(x)-i))=0,\max(supp(\sigma(x)))=b, (2)

where supp(g)𝑠𝑢𝑝𝑝𝑔supp(g) is the support of g𝑔g.

The following theorem is proved just as in the work E.Titmarsh [4].

Theorem 1.4 Let the condition  (2) hold. Then the number of zeros N(r)𝑁𝑟N(r) of the function Δ(λ)Δ𝜆\Delta(\lambda), which satisfy the inequality |λ|r𝜆𝑟|\lambda|\leq r, satisfies the limit inequality

limrN(r)r=bπ.𝑙𝑖subscript𝑚𝑟𝑁𝑟𝑟𝑏𝜋lim_{r\rightarrow\infty}\frac{N(r)}{r}=\frac{b}{\pi}.

In the work of M. Cartwright [5] it is shown that if σ(x)𝜎𝑥\sigma(x) satisfies  (2) and it is a function of a bounded variation, then all the zeros of the function Δ(λ)Δ𝜆\Delta(\lambda) are in a horizontal strip and the value of Nbrπ(r)𝑁𝑏𝑟𝜋𝑟N\frac{br}{\pi}(r) is bounded uniformly by r𝑟r.

2. Convolution, generated by operator L𝐿L

To obtain a convolution, we rewrite the resolvent (LλI)1superscript𝐿𝜆𝐼1(L-\lambda I)^{-1} in the form

(LλI)1f=i0xexp(iλ(xξ))Δ(λ)f(ξ)𝑑ξsuperscript𝐿𝜆𝐼1𝑓𝑖superscriptsubscript0𝑥𝑒𝑥𝑝𝑖𝜆𝑥𝜉Δ𝜆𝑓𝜉differential-d𝜉(L-\lambda I)^{-1}f=i\int_{0}^{x}\frac{exp(i\lambda(x-\xi))}{\Delta(\lambda)}f(\xi)d\xi
0bσ(μ)¯𝑑μμ(μxexp(iλ(xξ+μ))Δ(λ)f(ξ)𝑑ξ).superscriptsubscript0𝑏¯𝜎𝜇differential-d𝜇𝜇superscriptsubscript𝜇𝑥𝑒𝑥𝑝𝑖𝜆𝑥𝜉𝜇Δ𝜆𝑓𝜉differential-d𝜉-\int_{0}^{b}\overline{\sigma(\mu)}d\mu\frac{\partial}{\partial\mu}\Big{(}\int_{\mu}^{x}\frac{exp(i\lambda(x-\xi+\mu))}{\Delta(\lambda)}f(\xi)d\xi\Big{)}. (3)

Indeed, from the previous view of the resolvent  (1), we have the chain of equalities:

(LλI)1f=i0bexp(iλ(xξ))f(ξ)𝑑ξ+superscript𝐿𝜆𝐼1𝑓limit-from𝑖superscriptsubscript0𝑏𝑒𝑥𝑝𝑖𝜆𝑥𝜉𝑓𝜉differential-d𝜉(L-\lambda I)^{-1}f=i\int_{0}^{b}exp(i\lambda(x-\xi))f(\xi)d\xi+
+exp(iλx)Δ(λ)(0bf(x)σ(x)¯𝑑x+λi0bσ(x)¯𝑑x0xexp(iλ(xξ))f(ξ)𝑑ξ)=𝑒𝑥𝑝𝑖𝜆𝑥Δ𝜆superscriptsubscript0𝑏𝑓𝑥¯𝜎𝑥differential-d𝑥𝜆𝑖superscriptsubscript0𝑏¯𝜎𝑥differential-d𝑥superscriptsubscript0𝑥𝑒𝑥𝑝𝑖𝜆𝑥𝜉𝑓𝜉differential-d𝜉absent+\frac{exp(i\lambda x)}{\Delta(\lambda)}(\int_{0}^{b}f(x)\overline{\sigma(x)}dx+\lambda i\int_{0}^{b}\overline{\sigma(x)}dx\int_{0}^{x}exp(i\lambda(x-\xi))f(\xi)d\xi)=
=i0xexp(iλ(xξ))Δ(λ)f(ξ)𝑑ξ0bσ(μ)¯𝑑μ0xexp(iλ(xξ+μ))Δ(λ)f(ξ)𝑑ξ+absent𝑖superscriptsubscript0𝑥𝑒𝑥𝑝𝑖𝜆𝑥𝜉Δ𝜆𝑓𝜉differential-d𝜉limit-fromsuperscriptsubscript0𝑏¯𝜎𝜇differential-d𝜇superscriptsubscript0𝑥𝑒𝑥𝑝𝑖𝜆𝑥𝜉𝜇Δ𝜆𝑓𝜉differential-d𝜉=i\int_{0}^{x}\frac{exp(i\lambda(x-\xi))}{\Delta(\lambda)}f(\xi)d\xi-\int_{0}^{b}\overline{\sigma(\mu)}d\mu\int_{0}^{x}\frac{exp(i\lambda(x-\xi+\mu))}{\Delta(\lambda)}f(\xi)d\xi+
+0bexp(iλx)Δ(λ)f(ξ)σ(ξ)¯𝑑ξ+λi0bσ(μ)¯𝑑μ0μexp(iλ(xξ+μ))Δ(λ)f(ξ)𝑑ξ=superscriptsubscript0𝑏𝑒𝑥𝑝𝑖𝜆𝑥Δ𝜆𝑓𝜉¯𝜎𝜉differential-d𝜉𝜆𝑖superscriptsubscript0𝑏¯𝜎𝜇differential-d𝜇superscriptsubscript0𝜇𝑒𝑥𝑝𝑖𝜆𝑥𝜉𝜇Δ𝜆𝑓𝜉differential-d𝜉absent+\int_{0}^{b}\frac{exp(i\lambda x)}{\Delta(\lambda)}f(\xi)\overline{\sigma(\xi)}d\xi+\lambda i\int_{0}^{b}\overline{\sigma(\mu)}d\mu\int_{0}^{\mu}\frac{exp(i\lambda(x-\xi+\mu))}{\Delta(\lambda)}f(\xi)d\xi=
=i0xexp(iλ(xξ))Δ(λ)f(ξ)𝑑ξ0bσ(μ)¯𝑑μμxexp(iλ(xξ+μ))Δ(λ)f(ξ)𝑑ξ+absent𝑖superscriptsubscript0𝑥𝑒𝑥𝑝𝑖𝜆𝑥𝜉Δ𝜆𝑓𝜉differential-d𝜉limit-fromsuperscriptsubscript0𝑏¯𝜎𝜇differential-d𝜇superscriptsubscript𝜇𝑥𝑒𝑥𝑝𝑖𝜆𝑥𝜉𝜇Δ𝜆𝑓𝜉differential-d𝜉=i\int_{0}^{x}\frac{exp(i\lambda(x-\xi))}{\Delta(\lambda)}f(\xi)d\xi-\int_{0}^{b}\overline{\sigma(\mu)}d\mu\int_{\mu}^{x}\frac{exp(i\lambda(x-\xi+\mu))}{\Delta(\lambda)}f(\xi)d\xi+
+0bexp(iλx)Δ(λ)f(ξ)σ(ξ)¯𝑑ξ=superscriptsubscript0𝑏𝑒𝑥𝑝𝑖𝜆𝑥Δ𝜆𝑓𝜉¯𝜎𝜉differential-d𝜉absent+\int_{0}^{b}\frac{exp(i\lambda x)}{\Delta(\lambda)}f(\xi)\overline{\sigma(\xi)}d\xi=
=i0xexp(iλ(xξ))Δ(λ)f(ξ)𝑑ξ0bσ(μ)¯𝑑μμ(μxexp(iλ(xξ+μ))Δ(λ)f(ξ)𝑑ξ)absent𝑖superscriptsubscript0𝑥𝑒𝑥𝑝𝑖𝜆𝑥𝜉Δ𝜆𝑓𝜉differential-d𝜉superscriptsubscript0𝑏¯𝜎𝜇differential-d𝜇𝜇superscriptsubscript𝜇𝑥𝑒𝑥𝑝𝑖𝜆𝑥𝜉𝜇Δ𝜆𝑓𝜉differential-d𝜉=i\int_{0}^{x}\frac{exp(i\lambda(x-\xi))}{\Delta(\lambda)}f(\xi)d\xi-\int_{0}^{b}\overline{\sigma(\mu)}d\mu\frac{\partial}{\partial\mu}(\int_{\mu}^{x}\frac{exp(i\lambda(x-\xi+\mu))}{\Delta(\lambda)}f(\xi)d\xi)

This proves the lemma.

Lemma 2.1 The convolution, defined by the formula

(gf)(x):=i0xg(xξ)f(ξ)𝑑ξ0bσ(μ)¯𝑑μμ(μxg(xξ+μ)f(ξ)𝑑ξ)assign𝑔𝑓𝑥𝑖superscriptsubscript0𝑥𝑔𝑥𝜉𝑓𝜉differential-d𝜉superscriptsubscript0𝑏¯𝜎𝜇differential-d𝜇𝜇superscriptsubscript𝜇𝑥𝑔𝑥𝜉𝜇𝑓𝜉differential-d𝜉(g\ast f)(x):=i\int_{0}^{x}g(x-\xi)f(\xi)d\xi-\int_{0}^{b}\overline{\sigma(\mu)}d\mu\frac{\partial}{\partial\mu}(\int_{\mu}^{x}g(x-\xi+\mu)f(\xi)d\xi)

for g,fW21[0,b]𝑔𝑓subscriptsuperscript𝑊120𝑏g,f\in W^{1}_{2}[0,b] is bilinear, commutative and associative.

Proof. Let us introduce an operation \circ as

(gf)(x,t):=txg(xξ+μ)f(ξ)𝑑ξ,assign𝑔𝑓𝑥𝑡superscriptsubscript𝑡𝑥𝑔𝑥𝜉𝜇𝑓𝜉differential-d𝜉(g\circ f)(x,t):=\int_{t}^{x}g(x-\xi+\mu)f(\xi)d\xi,

then we can rewrite the expression gf𝑔𝑓g\ast f in the form

(gf)=i(gf)(x,0)0bμ(gf)(x,μ)σ(μ)¯𝑑μ=𝑔𝑓𝑖𝑔𝑓𝑥0superscriptsubscript0𝑏𝜇𝑔𝑓𝑥𝜇¯𝜎𝜇differential-d𝜇absent(g\ast f)=i(g\circ f)(x,0)-\int_{0}^{b}\frac{\partial}{\partial\mu}(g\circ f)(x,\mu)\overline{\sigma(\mu)}d\mu=
=i[(gf)(x,0)0b(iμ(gf)(x,μ))σ0(μ)¯𝑑μ]=iUt(gf)(x,t),absent𝑖delimited-[]𝑔𝑓𝑥0superscriptsubscript0𝑏𝑖𝜇𝑔𝑓𝑥𝜇¯subscript𝜎0𝜇differential-d𝜇𝑖subscript𝑈𝑡𝑔𝑓𝑥𝑡=i[(g\circ f)(x,0)-\int_{0}^{b}(-i\frac{\partial}{\partial\mu}(g\circ f)(x,\mu))\overline{\sigma_{0}(\mu)}d\mu]=iU_{t}(g\circ f)(x,t),

where

U(y)=y(0)0b(iμ)σ(μ)¯𝑑μ.𝑈𝑦𝑦0superscriptsubscript0𝑏𝑖𝜇¯𝜎𝜇differential-d𝜇U(y)=y(0)-\int_{0}^{b}(-i\frac{\partial}{\partial\mu})\overline{\sigma(\mu)}d\mu.

Hence, bilinearity is obvious. It is easy to see that the operation \circ is commutative. Indeed

(gf)(x,t)=txg(x+tξ)f(ξ)𝑑ξ=(ξ=x+tξdξ=dξxttx)=𝑔𝑓𝑥𝑡superscriptsubscript𝑡𝑥𝑔𝑥𝑡𝜉𝑓𝜉differential-d𝜉superscript𝜉𝑥𝑡𝜉𝑑𝜉𝑑superscript𝜉𝑥𝑡𝑡𝑥absent(g\circ f)(x,t)=\int_{t}^{x}g(x+t-\xi)f(\xi)d\xi=\left(\begin{array}[]{c}\xi^{\prime}=x+t-\xi\\ d\xi=-d\xi^{\prime}\\ x\rightarrow t\\ t\rightarrow x\\ \end{array}\right)=
=xtg(ξ)f(x+tξ)𝑑ξ=txf(x+tξ)g(ξ)𝑑ξ=(fg)(x,t)absentsuperscriptsubscript𝑥𝑡𝑔superscript𝜉𝑓𝑥𝑡superscript𝜉differential-dsuperscript𝜉superscriptsubscript𝑡𝑥𝑓𝑥𝑡𝜉𝑔𝜉differential-d𝜉𝑓𝑔𝑥𝑡=-\int_{x}^{t}g(\xi^{\prime})f(x+t-\xi^{\prime})d\xi^{\prime}=\int_{t}^{x}f(x+t-\xi)g(\xi)d\xi=(f\circ g)(x,t)

i.е.

(gf)(x,t)=(fg)(x,t)𝑔𝑓𝑥𝑡𝑓𝑔𝑥𝑡(g\circ f)(x,t)=(f\circ g)(x,t)

Then the operation \ast commutative too,

(gf)(x)=i(gf)(x,0)0bμ(gf)(x,μ)σ(μ)¯𝑑μ=𝑔𝑓𝑥𝑖𝑔𝑓𝑥0superscriptsubscript0𝑏𝜇𝑔𝑓𝑥𝜇¯𝜎𝜇differential-d𝜇absent(g\ast f)(x)=i(g\circ f)(x,0)-\int_{0}^{b}\frac{\partial}{\partial\mu}(g\circ f)(x,\mu)\overline{\sigma(\mu)}d\mu=
=i(fg)(x,0)0bμ(fg)(x,μ)σ(μ)¯𝑑μ=(fg)(x)absent𝑖𝑓𝑔𝑥0superscriptsubscript0𝑏𝜇𝑓𝑔𝑥𝜇¯𝜎𝜇differential-d𝜇𝑓𝑔𝑥=i(f\circ g)(x,0)-\int_{0}^{b}\frac{\partial}{\partial\mu}(f\circ g)(x,\mu)\overline{\sigma(\mu)}d\mu=(f\ast g)(x)

Remark 2.1 The convolution is expressed in terms of boundary conditions and has the form

(fg)(x)=iUμ{μxf(ξ)g(x+μξ)𝑑ξ},𝑓𝑔𝑥𝑖subscript𝑈𝜇superscriptsubscript𝜇𝑥𝑓𝜉𝑔𝑥𝜇𝜉differential-d𝜉(f\ast g)(x)=iU_{\mu}\{\int_{\mu}^{x}f(\xi)g(x+\mu-\xi)d\xi\}, (4)

where

U(y):=y(0)0b(idydx)σ(x)¯𝑑x.assign𝑈𝑦𝑦0subscriptsuperscript𝑏0𝑖𝑑𝑦𝑑𝑥¯𝜎𝑥differential-d𝑥U(y):=y(0)-\int^{b}_{0}(-i\frac{dy}{dx})\overline{\sigma(x)}dx.

Remark 2.2 From  (3) it is easy to see that the resolvent in terms of convolution is represented in the form

(LλI)1f=exp(iλx)Δ(λ)f(x).superscript𝐿𝜆𝐼1𝑓𝑒𝑥𝑝𝑖𝜆𝑥Δ𝜆𝑓𝑥(L-\lambda I)^{-1}f=\frac{exp(i\lambda x)}{\Delta(\lambda)}\ast f(x). (5)

Lemma 2.2 For any f𝑓f from the domain DLsubscript𝐷𝐿D_{L} and for arbitrary g𝑔g from W21[0,b],subscriptsuperscript𝑊120𝑏W^{1}_{2}[0,b], the equality

ddx(fg)=dfdxg𝑑𝑑𝑥𝑓𝑔𝑑𝑓𝑑𝑥𝑔\frac{d}{dx}(f\ast g)=\frac{df}{dx}\ast g

holds true.

Proof. Since the equality U(f)=0𝑈𝑓0U(f)=0 holds for fDL𝑓subscript𝐷𝐿f\in D_{L}, we get

ddx(fg)=if(0)g(x)+i0xdf(xξ)dxg(ξ)𝑑ξ𝑑𝑑𝑥𝑓𝑔𝑖𝑓0𝑔𝑥limit-from𝑖superscriptsubscript0𝑥𝑑𝑓𝑥𝜉𝑑𝑥𝑔𝜉differential-d𝜉\frac{d}{dx}(f\ast g)=if(0)g(x)+i\int_{0}^{x}\frac{df(x-\xi)}{dx}g(\xi)d\xi-
0bσ(μ)¯𝑑μμ(f(μ)g(x)+μxxf(xξ+μ)g(ξ)𝑑ξ)=dfdxg+if(0)g(x)subscriptsuperscript𝑏0¯𝜎𝜇differential-d𝜇𝜇matrix𝑓𝜇𝑔𝑥superscriptsubscript𝜇𝑥𝑥𝑓𝑥𝜉𝜇𝑔𝜉differential-d𝜉𝑑𝑓𝑑𝑥𝑔limit-from𝑖𝑓0𝑔𝑥-\int^{b}_{0}\overline{\sigma(\mu)}d\mu\frac{\partial}{\partial\mu}\begin{pmatrix}f(\mu)g(x)+\int_{\mu}^{x}\frac{\partial}{\partial x}f(x-\xi+\mu)g(\xi)d\xi\\ \end{pmatrix}=\frac{df}{dx}\ast g+if(0)g(x)-
0bσ0(x)¯μf(μ)g(x)𝑑μ=dfdxg+ig(x)U(f)=dfdxg.subscriptsuperscript𝑏0¯subscript𝜎0𝑥𝜇𝑓𝜇𝑔𝑥differential-d𝜇𝑑𝑓𝑑𝑥𝑔𝑖𝑔𝑥𝑈𝑓𝑑𝑓𝑑𝑥𝑔-\int^{b}_{0}\overline{\sigma_{0}(x)}\frac{\partial}{\partial\mu}f(\mu)g(x)d\mu=\frac{df}{dx}\ast g+ig(x)U(f)=\frac{df}{dx}\ast g.

Lemma 2.3 The convolution defined in Lemma 2.1 is without annihilators, i.e. if for arbitrary

gW21[0,b]𝑔subscriptsuperscript𝑊120𝑏g\in W^{1}_{2}[0,b]

and for some fL2(0,b)𝑓subscript𝐿20𝑏f\in L_{2}(0,b) the equality

(gf)(x)=0𝑔𝑓𝑥0(g\ast f)(x)=0

holds, then f𝑓f is identically equal to zero.

Proof. Let (gf)(x)=0𝑔𝑓𝑥0(g\ast f)(x)=0, fL2(0,b),𝑓subscript𝐿20𝑏f\in L_{2}(0,b), then we take

g=:exp(iλx)Δ(λ)|λ=0=1.g=:\frac{exp(i\lambda x)}{\Delta(\lambda)}|_{\lambda=0}=1.

By the definition of our convolution, the expression 1f=01𝑓01\ast f=0 denotes the equality L1f=0superscript𝐿1𝑓0L^{-1}f=0. Denoting L1fsuperscript𝐿1𝑓L^{-1}f by y𝑦y, we obtain respectively Ly=f,𝐿𝑦𝑓Ly=f, but y=0𝑦0y=0, hence, as the L𝐿L a linear operator, it follows that f=0𝑓0f=0.

Lemma 2.4 If the function f𝑓f is from the domain DLsubscript𝐷𝐿D_{L} of the operator L𝐿L, then for each gL2(0,b)𝑔subscript𝐿20𝑏g\in L_{2}(0,b) the convolution fg𝑓𝑔f\ast g will also belong to the domain DLsubscript𝐷𝐿D_{L}.

Proof. Let

f=:exp(iλ0x)Δ(λ0)|λ0=0=1.f=:\frac{exp(i\lambda_{0}x)}{\Delta(\lambda_{0})}|_{\lambda_{0}=0}=1.

Let us denote by y𝑦y the function y=1g𝑦1𝑔y=1\ast g, by construction of the convolution this expression means that y=L1g𝑦superscript𝐿1𝑔y=L^{-1}g i.e. Ly=g𝐿𝑦𝑔Ly=g, which implies yDL𝑦subscript𝐷𝐿y\in D_{L}. Now we fix any λ𝜆\lambda such that Δ(λ)0Δ𝜆0\Delta(\lambda)\neq 0. Let f=:exp(iλx)Δ(λ)f=:\frac{exp(i\lambda x)}{\Delta(\lambda)}.

If by y𝑦y we denote y=1g𝑦1𝑔y=1\ast g, then this expression by the convolution construction mean that y=L1g,𝑦superscript𝐿1𝑔y=L^{-1}g, i.e. Ly=g𝐿𝑦𝑔Ly=g, and implies yDL.𝑦subscript𝐷𝐿y\in D_{L}. Now we fix any λ𝜆\lambda, such that Δ(λ)0Δ𝜆0\Delta(\lambda)\neq 0. Let f=:exp(iλx)Δ(λ)f=:\frac{exp(i\lambda x)}{\Delta(\lambda)}. Let y𝑦y denote the convolution y=exp(iλx)Δ(λ)g𝑦𝑒𝑥𝑝𝑖𝜆𝑥Δ𝜆𝑔y=\frac{exp(i\lambda x)}{\Delta(\lambda)}\ast g, then from the definition of the convolution, we get y=(LλI)1g,𝑦superscript𝐿𝜆𝐼1𝑔y=(L-\lambda I)^{-1}g, i.e. Ly=λy+g𝐿𝑦𝜆𝑦𝑔Ly=\lambda y+g for any λ𝜆\lambda. Since zeros of the function Δ(λ)Δ𝜆\Delta(\lambda) are countable set, then there is sequence {λn}subscript𝜆𝑛\{\lambda_{n}\} such that Δ(λn)0Δsubscript𝜆𝑛0\Delta(\lambda_{n})\neq 0 and the system exp(iλnx)𝑒𝑥𝑝𝑖subscript𝜆𝑛𝑥exp(i\lambda_{n}x) is basis in the space W21[0,b]subscriptsuperscript𝑊120𝑏W^{1}_{2}[0,b]. For any natural number n𝑛n it is λnsubscript𝜆𝑛\lambda_{n} such that the convolution exp(iλnx)g𝑒𝑥𝑝𝑖subscript𝜆𝑛𝑥𝑔exp(i\lambda_{n}x)\ast g will belong to the domain DLsubscript𝐷𝐿D_{L}. From f(x)=n=0cnexp(iλnx)𝑓𝑥superscriptsubscript𝑛0subscript𝑐𝑛𝑒𝑥𝑝𝑖subscript𝜆𝑛𝑥f(x)=\sum_{n=0}^{\infty}c_{n}exp(i\lambda_{n}x) and from the bilinearity of the convolution, the convolution fg𝑓𝑔f\ast g belongs to the domain DLsubscript𝐷𝐿D_{L}.

Lemma 2.5 For arbitrary λ𝜆\lambda and β𝛽\beta such that λβ𝜆𝛽\lambda\neq\beta we have the equality

exp(iλx)exp(iβx)=exp(iβx)Δ(λ)exp(iλx)Δ(β)βλ.𝑒𝑥𝑝𝑖𝜆𝑥𝑒𝑥𝑝𝑖𝛽𝑥𝑒𝑥𝑝𝑖𝛽𝑥Δ𝜆𝑒𝑥𝑝𝑖𝜆𝑥Δ𝛽𝛽𝜆exp(i\lambda x)\ast exp(i\beta x)=\frac{exp(i\beta x)\Delta(\lambda)-exp(i\lambda x)\Delta(\beta)}{\beta-\lambda}.

Proof. We write by definition

exp(iλx)exp(iβx)=𝑒𝑥𝑝𝑖𝜆𝑥𝑒𝑥𝑝𝑖𝛽𝑥absentexp(i\lambda x)\ast exp(i\beta x)=
=i0xexp(iλ(xξ))exp(iβξ)𝑑ξabsentlimit-from𝑖superscriptsubscript0𝑥𝑒𝑥𝑝𝑖𝜆𝑥𝜉𝑒𝑥𝑝𝑖𝛽𝜉differential-d𝜉=i\int_{0}^{x}exp(i\lambda(x-\xi))exp(i\beta\xi)d\xi-
0bσ(μ)¯𝑑μμ(μxexp(iλ(xξ+μ))exp(iβξ)𝑑ξ)=subscriptsuperscript𝑏0¯𝜎𝜇differential-d𝜇𝜇matrixsuperscriptsubscript𝜇𝑥𝑒𝑥𝑝𝑖𝜆𝑥𝜉𝜇𝑒𝑥𝑝𝑖𝛽𝜉differential-d𝜉absent-\int^{b}_{0}\overline{\sigma(\mu)}d\mu\frac{\partial}{\partial\mu}\begin{pmatrix}\int_{\mu}^{x}exp(i\lambda(x-\xi+\mu))exp(i\beta\xi)d\xi\\ \end{pmatrix}=
=iexp(iλx)(exp(i(βλ)x)1)i(βλ)absentlimit-from𝑖𝑒𝑥𝑝𝑖𝜆𝑥𝑒𝑥𝑝𝑖𝛽𝜆𝑥1𝑖𝛽𝜆=\frac{iexp(i\lambda x)(exp(i(\beta-\lambda)x)-1)}{i(\beta-\lambda)}-
0bσ(μ)¯𝑑μμ(exp(iλ(x+μ))exp(i(βλ)x)exp(i(βλ)μ)i(βλ))=subscriptsuperscript𝑏0¯𝜎𝜇differential-d𝜇𝜇matrix𝑒𝑥𝑝𝑖𝜆𝑥𝜇𝑒𝑥𝑝𝑖𝛽𝜆𝑥𝑒𝑥𝑝𝑖𝛽𝜆𝜇𝑖𝛽𝜆absent-\int^{b}_{0}\overline{\sigma(\mu)}d\mu\frac{\partial}{\partial\mu}\begin{pmatrix}exp(i\lambda(x+\mu))\frac{exp(i(\beta-\lambda)x)-exp(i(\beta-\lambda)\mu)}{i(\beta-\lambda)}\\ \end{pmatrix}=
=exp(iβx)exp(iλx)βλabsentlimit-from𝑒𝑥𝑝𝑖𝛽𝑥𝑒𝑥𝑝𝑖𝜆𝑥𝛽𝜆=\frac{exp(i\beta x)-exp(i\lambda x)}{\beta-\lambda}-
0bσ(μ)¯𝑑μμ[exp(iλμ)exp(iβx)exp(iλx)exp(iβμ)i(βλ)]=subscriptsuperscript𝑏0¯𝜎𝜇differential-d𝜇𝜇matrix𝑒𝑥𝑝𝑖𝜆𝜇𝑒𝑥𝑝𝑖𝛽𝑥𝑒𝑥𝑝𝑖𝜆𝑥𝑒𝑥𝑝𝑖𝛽𝜇𝑖𝛽𝜆absent-\int^{b}_{0}\overline{\sigma(\mu)}d\mu\frac{\partial}{\partial\mu}\begin{bmatrix}\frac{exp(i\lambda\mu)exp(i\beta x)-exp(i\lambda x)exp(i\beta\mu)}{i(\beta-\lambda)}\\ \end{bmatrix}=
=exp(iβx)exp(iλx)βλabsentlimit-from𝑒𝑥𝑝𝑖𝛽𝑥𝑒𝑥𝑝𝑖𝜆𝑥𝛽𝜆=\frac{exp(i\beta x)-exp(i\lambda x)}{\beta-\lambda}-
0biλexp(iλμ)exp(iβx)iβexp(iλx)exp(iβμ)i(βλ)σ(μ)¯𝑑μ=subscriptsuperscript𝑏0𝑖𝜆𝑒𝑥𝑝𝑖𝜆𝜇𝑒𝑥𝑝𝑖𝛽𝑥𝑖𝛽𝑒𝑥𝑝𝑖𝜆𝑥𝑒𝑥𝑝𝑖𝛽𝜇𝑖𝛽𝜆¯𝜎𝜇differential-d𝜇absent-\int^{b}_{0}\frac{i\lambda exp(i\lambda\mu)exp(i\beta x)-i\beta exp(i\lambda x)exp(i\beta\mu)}{i(\beta-\lambda)}\overline{\sigma(\mu)}d\mu=
1βλ[exp(iβx)exp(iλx)λexp(iβx)0bexp(iλμ)σ(μ)¯dμ+\frac{1}{\beta-\lambda}[exp(i\beta x)-exp(i\lambda x)-\lambda exp(i\beta x)\int^{b}_{0}exp(i\lambda\mu)\overline{\sigma(\mu)}d\mu+
+βexp(iλx)0bexp(iβμ)σ(μ)¯dμ]=exp(iβx)Δ(λ)exp(iλx)Δ(β)βλ.+\beta exp(i\lambda x)\int^{b}_{0}exp(i\beta\mu)\overline{\sigma(\mu)}d\mu]=\frac{exp(i\beta x)\Delta(\lambda)-exp(i\lambda x)\Delta(\beta)}{\beta-\lambda}.

3. Fourier transform and convolution

For any function f𝑓f from the space L2(0,b),subscript𝐿20𝑏L_{2}(0,b), let us associate the expansion

fλnσ(L)Pnf,similar-to𝑓subscriptsubscript𝜆𝑛𝜎𝐿subscript𝑃𝑛𝑓f\sim\sum_{\lambda_{n}\in\sigma(L)}P_{n}f,

where the orthogonal projection is given by

Pnf=12πi|λλn|=δ(LλI)1f𝑑λ.subscript𝑃𝑛𝑓12𝜋𝑖subscriptcontour-integral𝜆subscript𝜆𝑛𝛿superscript𝐿𝜆𝐼1𝑓differential-d𝜆P_{n}f=-\frac{1}{2\pi i}\oint_{|\lambda-\lambda_{n}|=\delta}(L-\lambda I)^{-1}fd\lambda.

By using  (5) we obtain

Pnf=resλnexp(iλx)Δ(λ)f=[1(mn1)!limλλnmn1λmn1((λλn)mnΔ(λ)exp(iλx))]f(x)=subscript𝑃𝑛𝑓𝑟𝑒subscript𝑠subscript𝜆𝑛𝑒𝑥𝑝𝑖𝜆𝑥Δ𝜆𝑓delimited-[]1subscript𝑚𝑛1𝑙𝑖subscript𝑚𝜆subscript𝜆𝑛superscriptsubscript𝑚𝑛1superscript𝜆subscript𝑚𝑛1superscript𝜆subscript𝜆𝑛subscript𝑚𝑛Δ𝜆𝑒𝑥𝑝𝑖𝜆𝑥𝑓𝑥absentP_{n}f=res_{\lambda_{n}}\frac{exp(i\lambda x)}{\Delta(\lambda)}\ast f=[\frac{1}{(m_{n}-1)!}lim_{\lambda\rightarrow\lambda_{n}}\frac{\partial^{m_{n}-1}}{\partial\lambda^{m_{n}-1}}(\frac{(\lambda-\lambda_{n})^{m_{n}}}{\Delta(\lambda)}exp(i\lambda x))]\ast f(x)=
=[j=0mn1dj,nj!((ix)mn1j(mn1j)!exp(iλnx))]f(x).absentdelimited-[]superscriptsubscript𝑗0subscript𝑚𝑛1subscript𝑑𝑗𝑛𝑗superscript𝑖𝑥subscript𝑚𝑛1𝑗subscript𝑚𝑛1𝑗𝑒𝑥𝑝𝑖subscript𝜆𝑛𝑥𝑓𝑥=[\sum_{j=0}^{m_{n}-1}\frac{d_{j,n}}{j!}(\frac{(ix)^{m_{n}-1-j}}{(m_{n}-1-j)!}exp(i\lambda_{n}x))]\ast f(x).

Let us define

umn1,n:=j=0mn1dj,nj!((ix)mn1j(mn1j)!exp(iλnx)),assignsubscript𝑢subscript𝑚𝑛1𝑛superscriptsubscript𝑗0subscript𝑚𝑛1subscript𝑑𝑗𝑛𝑗superscript𝑖𝑥subscript𝑚𝑛1𝑗subscript𝑚𝑛1𝑗𝑒𝑥𝑝𝑖subscript𝜆𝑛𝑥u_{m_{n}-1,n}:=\sum_{j=0}^{m_{n}-1}\frac{d_{j,n}}{j!}(\frac{(ix)^{m_{n}-1-j}}{(m_{n}-1-j)!}exp(i\lambda_{n}x)), (6)

where {dj,n}subscript𝑑𝑗𝑛\{d_{j,n}\} are the expansion coefficients in the Taylor series of the function (λλn)mnΔ(λ)superscript𝜆subscript𝜆𝑛subscript𝑚𝑛Δ𝜆\frac{(\lambda-\lambda_{n})^{m_{n}}}{\Delta(\lambda)} in front of powers of (λλn).𝜆subscript𝜆𝑛(\lambda-\lambda_{n}). Then

Pnf=umn1,nf.subscript𝑃𝑛𝑓subscript𝑢subscript𝑚𝑛1𝑛𝑓P_{n}f=u_{m_{n}-1,n}\ast f. (7)

Let us introduce a system of root functions of the operator L𝐿L corresponding to the eigenvalue λnsubscript𝜆𝑛\lambda_{n} by the expression

us,n:=Lus+1,nλnus+1,n=j=0sdj,nj!(ix)sj(sj)!exp(iλnx),s=0,..,mn2.u_{s,n}:=Lu_{s+1,n}-\lambda_{n}u_{s+1,n}=\sum_{j=0}^{s}\frac{d_{j,n}}{j!}\frac{(ix)^{s-j}}{(s-j)!}exp(i\lambda_{n}x),\,\,\,s=0,.....,m_{n}-2. (8)

Lemma 3.1 The system of root functions {uk,n,k=0,mn1}formulae-sequencesubscript𝑢𝑘𝑛𝑘0subscript𝑚𝑛1\{u_{k,n},k=0...,m_{n}-1\} is linearly independent.

Proof. Consider the linear combination

α0u0,n++αmn2umn2,n+αmn1umn1,n=0.subscript𝛼0subscript𝑢0𝑛subscript𝛼subscript𝑚𝑛2subscript𝑢subscript𝑚𝑛2𝑛subscript𝛼subscript𝑚𝑛1subscript𝑢subscript𝑚𝑛1𝑛0\alpha_{0}u_{0,n}+...+\alpha_{m_{n}-2}u_{m_{n}-2,n}+\alpha_{m_{n}-1}u_{m_{n}-1,n}=0. (9)

It is easy to see that

(LλnI)mn1us,n=0.s=0,,mn2.formulae-sequencesuperscript𝐿subscript𝜆𝑛𝐼subscript𝑚𝑛1subscript𝑢𝑠𝑛0𝑠0subscript𝑚𝑛2(L-\lambda_{n}I)^{m_{n}-1}u_{s,n}=0.s=0,...,m_{n}-2. (10)

By applying to  (9) the operator (LλnI)mn1superscript𝐿subscript𝜆𝑛𝐼subscript𝑚𝑛1(L-\lambda_{n}I)^{m_{n}-1} on both sides, we get

αmn1(LλnI)mn1umn1,n=0.subscript𝛼subscript𝑚𝑛1superscript𝐿subscript𝜆𝑛𝐼subscript𝑚𝑛1subscript𝑢subscript𝑚𝑛1𝑛0\alpha_{m_{n}-1}(L-\lambda_{n}I)^{m_{n}-1}u_{m_{n}-1,n}=0. (11)

From  (8) we see that  (11) is equivalent to

αmn1u0,n=0.subscript𝛼subscript𝑚𝑛1subscript𝑢0𝑛0\alpha_{m_{n}-1}u_{0,n}=0.

Since d0,n0subscript𝑑0𝑛0d_{0,n}\neq 0, we obtain

αmn1=0.subscript𝛼subscript𝑚𝑛10\alpha_{m_{n}-1}=0.

Now we consider the equality  (9) with αmn1=0subscript𝛼subscript𝑚𝑛10\alpha_{m_{n}-1}=0, i.e.

α0u0,n++αmn2umn2,n=0.subscript𝛼0subscript𝑢0𝑛subscript𝛼subscript𝑚𝑛2subscript𝑢subscript𝑚𝑛2𝑛0\alpha_{0}u_{0,n}+...+\alpha_{m_{n}-2}u_{m_{n}-2,n}=0.

Applying to both sides the operator (LλnI)mn2superscript𝐿subscript𝜆𝑛𝐼subscript𝑚𝑛2(L-\lambda_{n}I)^{m_{n}-2} and using  (10) as in the previous step, we get

αmn2u0,n=0,subscript𝛼subscript𝑚𝑛2subscript𝑢0𝑛0\alpha_{m_{n}-2}u_{0,n}=0,

whence αmn2=0.subscript𝛼subscript𝑚𝑛20\alpha_{m_{n}-2}=0.

Repeating these steps, we find that equality  (9) is true only for αk=0,k=0,,mn1formulae-sequencesubscript𝛼𝑘0𝑘0subscript𝑚𝑛1\alpha_{k}=0,k=0,...,m_{n}-1. This proves the linear independence of the system {uk,n,k=0,mn1}formulae-sequencesubscript𝑢𝑘𝑛𝑘0subscript𝑚𝑛1\{u_{k,n},k=0...,m_{n}-1\}.

Since d0,n0subscript𝑑0𝑛0d_{0,n}\neq 0, the system u0,n,u1,n,,umn1,nsubscript𝑢0𝑛subscript𝑢1𝑛subscript𝑢subscript𝑚𝑛1𝑛u_{0,n},u_{1,n},...,u_{m_{n}-1,n} is linearly independent and, therefore, there is a basis of the root subspace

Hλn:=Ker(LλnI)mn.assignsubscript𝐻subscript𝜆𝑛𝐾𝑒𝑟superscript𝐿subscript𝜆𝑛𝐼subscript𝑚𝑛H_{\lambda_{n}}:=Ker(L-\lambda_{n}I)^{m_{n}}.

We expand the function Pnfsubscript𝑃𝑛𝑓P_{n}f on Ker(LλnI)mn𝐾𝑒𝑟superscript𝐿subscript𝜆𝑛𝐼subscript𝑚𝑛Ker(L-\lambda_{n}I)^{m_{n}} by this basis

Pnf=Cmn1,n(f)u0,n+Cmn2,n(f)u1,n++C0,n(f)umn1,n.subscript𝑃𝑛𝑓subscript𝐶subscript𝑚𝑛1𝑛𝑓subscript𝑢0𝑛subscript𝐶subscript𝑚𝑛2𝑛𝑓subscript𝑢1𝑛subscript𝐶0𝑛𝑓subscript𝑢subscript𝑚𝑛1𝑛P_{n}f=C_{m_{n}-1,n}(f)u_{0,n}+C_{m_{n}-2,n}(f)u_{1,n}+...+C_{0,n}(f)u_{m_{n}-1,n}.

Thus, for each element f𝑓f of the space L2(0,b)subscript𝐿20𝑏L_{2}(0,b) we associate the element of the sequence space

{(C0,n(f),,Cmn1,n(f)),λnσ(L)}λnσ(L)mn,subscript𝐶0𝑛𝑓subscript𝐶subscript𝑚𝑛1𝑛𝑓subscript𝜆𝑛𝜎𝐿subscriptproductsubscript𝜆𝑛𝜎𝐿superscriptsubscript𝑚𝑛\{(C_{0,n}(f),...,C_{m_{n}-1,n}(f)),\lambda_{n}\in\sigma(L)\}\in\prod_{\lambda_{n}\in\sigma(L)}\mathbb{C}^{m_{n}},

i.e. we introduce the Fourier transform

f^={(C0,n(f),,Cmn1,n(f)),λnσ(L)}.^𝑓subscript𝐶0𝑛𝑓subscript𝐶subscript𝑚𝑛1𝑛𝑓subscript𝜆𝑛𝜎𝐿\widehat{f}=\{(C_{0,n}(f),...,C_{m_{n}-1,n}(f)),\lambda_{n}\in\sigma(L)\}.

In the space of sequences, we introduce the inner Cauchy convolution. Let ξ𝜉\xi and η𝜂\eta be any elements of the X:=λnσ(L)mnassign𝑋subscriptproductsubscript𝜆𝑛𝜎𝐿superscriptsubscript𝑚𝑛X:=\prod_{\lambda_{n}\in\sigma(L)}\mathbb{C}^{m_{n}}, then we will call their convolution the sequence

μ:={(ξ0,nη0,n;ξ0,nη1,n+ξ1,nη0,n;,k=0mn1ξk,nηmn1k,n),λnσ(L)},assign𝜇subscript𝜉0𝑛subscript𝜂0𝑛subscript𝜉0𝑛subscript𝜂1𝑛subscript𝜉1𝑛subscript𝜂0𝑛superscriptsubscript𝑘0subscript𝑚𝑛1subscript𝜉𝑘𝑛subscript𝜂subscript𝑚𝑛1𝑘𝑛subscript𝜆𝑛𝜎𝐿\mu:=\{(\xi_{0,n}\eta_{0,n};\xi_{0,n}\eta_{1,n}+\xi_{1,n}\eta_{0,n};...,\sum_{k=0}^{m_{n}-1}\xi_{k,n}\eta_{m_{n}-1-k,n}),\lambda_{n}\in\sigma(L)\},

which we denote by ξXηsubscript𝑋𝜉𝜂\xi\ast_{X}\eta. Introduced convolutions Xsubscript𝑋\ast_{X} and \ast are associated between themselves by the Fourier transform.

Theorem 3.1 For arbitrary functions f𝑓f and g𝑔g from the space W21[0,b]subscriptsuperscript𝑊120𝑏W^{1}_{2}[0,b] the equality

fg^=f^Xg^^𝑓𝑔subscript𝑋^𝑓^𝑔\widehat{f\ast g}=\widehat{f}\ast_{X}\widehat{g} (12)

holds.

Proof. Let f=umn1,n𝑓subscript𝑢subscript𝑚𝑛1𝑛f=u_{m_{n}-1,n}. Then the equality umn1,ng^=u^mn1,nXg^^subscript𝑢subscript𝑚𝑛1𝑛𝑔subscript𝑋subscript^𝑢subscript𝑚𝑛1𝑛^𝑔\widehat{u_{m_{n}-1,n}\ast g}=\widehat{u}_{m_{n}-1,n}\ast_{X}\widehat{g} follows from the following chain of equalities

(umn1,ng)^=(Png)^=(C0,n(g),C1,n(g),,Cmn1,n(g))=subscript𝑢subscript𝑚𝑛1𝑛𝑔^absentsubscript𝑃𝑛𝑔^absentsubscript𝐶0𝑛𝑔subscript𝐶1𝑛𝑔subscript𝐶subscript𝑚𝑛1𝑛𝑔absent(u_{m_{n}-1,n}\ast g)\hat{}=(P_{n}g)\hat{}=(C_{0,n}(g),C_{1,n}(g),...,C_{m_{n}-1,n}(g))=
=(1,0,,0)X(C0,n(g),C1,n(g),,Cmn1,n(g)).absentsubscript𝑋100subscript𝐶0𝑛𝑔subscript𝐶1𝑛𝑔subscript𝐶subscript𝑚𝑛1𝑛𝑔=(1,0,...,0)\ast_{X}(C_{0,n}(g),C_{1,n}(g),...,C_{m_{n}-1,n}(g)).

Let now f=us,n𝑓subscript𝑢𝑠𝑛f=u_{s,n}, then

(us,ng)^=((LλnI)mn1sumn1,ng)^=subscript𝑢𝑠𝑛𝑔^absentsuperscript𝐿subscript𝜆𝑛𝐼subscript𝑚𝑛1𝑠subscript𝑢subscript𝑚𝑛1𝑛𝑔^absentabsent(u_{s,n}\ast g)\hat{}=((L-\lambda_{n}I)^{m_{n}-1-s}u_{m_{n}-1,n}\ast g)\hat{}=
=((LλnI)mn1s(umn1,ng))^=((LλnI)mn1sPng))^=(Pn(LλnI)mn1sg))^==((L-\lambda_{n}I)^{m_{n}-1-s}(u_{m_{n}-1,n}\ast g))\hat{}=((L-\lambda_{n}I)^{m_{n}-1-s}P_{n}g))\hat{}=(P_{n}(L-\lambda_{n}I)^{m_{n}-1-s}g))\hat{}=
=(C0,n)(LλnI)mn1sg)),(C1,n)(LλnI)mn1sg)),,(Cmn1,n)(LλnI)mn1sg)).=(C_{0,n})(L-\lambda_{n}I)^{m_{n}-1-s}g)),(C_{1,n})(L-\lambda_{n}I)^{m_{n}-1-s}g)),...,(C_{m_{n}-1,n})(L-\lambda_{n}I)^{m_{n}-1-s}g)).

On the other hand, the relations

Cmn1,n((LλnI)g)=Cmn2,n(g),subscript𝐶subscript𝑚𝑛1𝑛𝐿subscript𝜆𝑛𝐼𝑔subscript𝐶subscript𝑚𝑛2𝑛𝑔C_{m_{n}-1,n}((L-\lambda_{n}I)g)=C_{m_{n}-2,n}(g),
,...,
C1,n((LλnI)g)=C0,n(g)subscript𝐶1𝑛𝐿subscript𝜆𝑛𝐼𝑔subscript𝐶0𝑛𝑔C_{1,n}((L-\lambda_{n}I)g)=C_{0,n}(g)

and

C0,n((LλnI)g)=0subscript𝐶0𝑛𝐿subscript𝜆𝑛𝐼𝑔0C_{0,n}((L-\lambda_{n}I)g)=0

are valid, i.e. the action of the operator (LλnI)𝐿subscript𝜆𝑛𝐼(L-\lambda_{n}I) is equivalent to a shift in the sequence space. Then action of the operator (LλnI)mn1ssuperscript𝐿subscript𝜆𝑛𝐼subscript𝑚𝑛1𝑠(L-\lambda_{n}I)^{m_{n}-1-s} corresponds to a shift to the right on mn1ssubscript𝑚𝑛1𝑠m_{n}-1-s position. This implies the equality

us,ng^=us,n^Xg^,s=0,,mn1.formulae-sequence^subscript𝑢𝑠𝑛𝑔subscript𝑋^subscript𝑢𝑠𝑛^𝑔𝑠0subscript𝑚𝑛1\widehat{u_{s,n}\ast g}=\widehat{u_{s,n}}\ast_{X}\widehat{g},\,\,\,s=0,...,m_{n}-1.

From the fact that the theorem holds for all elements of the basis {us,n}subscript𝑢𝑠𝑛\{u_{s,n}\} follows the required equality  (12) follow in the whole space.

4. Coefficient functionals and a boundary condition

Elements of the basis of the each root subspace have good properties.

Lemma 4.1 Let λnsubscript𝜆𝑛\lambda_{n} be zeros of the entire function Δ(λ)Δ𝜆\Delta(\lambda) with corresponding multiplicities mnsubscript𝑚𝑛m_{n}. Then the elements  (6) and  (8) of the root subspace Hλnsubscript𝐻subscript𝜆𝑛H_{\lambda_{n}} have the following properties:

up,nuq,n={0,for p+q<mn1,up+qmn+1,for p+qmn1,subscript𝑢𝑝𝑛subscript𝑢𝑞𝑛cases0for p+q<mn1subscript𝑢𝑝𝑞subscript𝑚𝑛1for p+qmn1,u_{p,n}\ast u_{q,n}=\begin{cases}0,&\text{for $p+q<m_{n}-1$},\\ u_{p+q-m_{n}+1},&\text{for $p+q\geq m_{n}-1$,}\\ \end{cases} (13)

0p,qmn1.formulae-sequence0𝑝𝑞subscript𝑚𝑛10\leq p,q\leq m_{n}-1.

Proof. At first, we note that the element  (6) is idempotent with respect to the convolution, i.e.

umn1,numn1,n=umn1,n.subscript𝑢subscript𝑚𝑛1𝑛subscript𝑢subscript𝑚𝑛1𝑛subscript𝑢subscript𝑚𝑛1𝑛u_{m_{n}-1,n}\ast u_{m_{n}-1,n}=u_{m_{n}-1,n}.

By acting on the element umn1,nsubscript𝑢subscript𝑚𝑛1𝑛u_{m_{n}-1,n} of the basis of root subspace of the operator Pnsubscript𝑃𝑛P_{n}, we get

Pn(umn1,n)=umn1,n.subscript𝑃𝑛subscript𝑢subscript𝑚𝑛1𝑛subscript𝑢subscript𝑚𝑛1𝑛P_{n}(u_{m_{n}-1,n})=u_{m_{n}-1,n}.

On the other hand, by replacing the function f𝑓f by umn1,nsubscript𝑢subscript𝑚𝑛1𝑛u_{m_{n}-1,n} in the formula  (7), we have

Pn(umn1,n)=umn1,numn1,n,subscript𝑃𝑛subscript𝑢subscript𝑚𝑛1𝑛subscript𝑢subscript𝑚𝑛1𝑛subscript𝑢subscript𝑚𝑛1𝑛P_{n}(u_{m_{n}-1,n})=u_{m_{n}-1,n}\ast u_{m_{n}-1,n},

which proves the property that the element umn1,nsubscript𝑢subscript𝑚𝑛1𝑛u_{m_{n}-1,n} is idempotent. Further, from  (8) it is easy to see that each basis element can be presented by an idempotent element umn1,nsubscript𝑢subscript𝑚𝑛1𝑛u_{m_{n}-1,n} in the form

uq,n=(LλnI)mn1qumn1,n,q=0,,mn2.formulae-sequencesubscript𝑢𝑞𝑛superscript𝐿subscript𝜆𝑛𝐼subscript𝑚𝑛1𝑞subscript𝑢subscript𝑚𝑛1𝑛𝑞0subscript𝑚𝑛2u_{q,n}=(L-\lambda_{n}I)^{m_{n}-1-q}u_{m_{n}-1,n},q=0,...,m_{n}-2. (14)

Then consider the convolution of two elements of the basis

uq,nup,n=[(LλnI)mn1qumn1,n][(LλnI)mn1pumn1,n]=subscript𝑢𝑞𝑛subscript𝑢𝑝𝑛delimited-[]superscript𝐿subscript𝜆𝑛𝐼subscript𝑚𝑛1𝑞subscript𝑢subscript𝑚𝑛1𝑛delimited-[]superscript𝐿subscript𝜆𝑛𝐼subscript𝑚𝑛1𝑝subscript𝑢subscript𝑚𝑛1𝑛absentu_{q,n}\ast u_{p,n}=[(L-\lambda_{n}I)^{m_{n}-1-q}u_{m_{n}-1,n}]\ast[(L-\lambda_{n}I)^{m_{n}-1-p}u_{m_{n}-1,n}]=

|by using bilinear property of the convolution \ast|

=(LλnI)2mn2qp(umn1,numn1,n)=absentsuperscript𝐿subscript𝜆𝑛𝐼2subscript𝑚𝑛2𝑞𝑝subscript𝑢subscript𝑚𝑛1𝑛subscript𝑢subscript𝑚𝑛1𝑛absent=(L-\lambda_{n}I)^{2m_{n}-2-q-p}(u_{m_{n}-1,n}\ast u_{m_{n}-1,n})=

|by using idempotence property of the element umn1,nsubscript𝑢subscript𝑚𝑛1𝑛u_{m_{n}-1,n}|

=(LλnI)mn1(q+pmn+1umn1,n.=(L-\lambda_{n}I)^{m_{n}-1-(q+p-m_{n}+1}u_{m_{n}-1,n}.

It is clear that if the inequality q+pmn+10𝑞𝑝subscript𝑚𝑛10q+p-m_{n}+1\geq 0 holds, then from  (14) it follows that

up,nuq,n=up+qmn+1,nsubscript𝑢𝑝𝑛subscript𝑢𝑞𝑛subscript𝑢𝑝𝑞subscript𝑚𝑛1𝑛u_{p,n}\ast u_{q,n}=u_{p+q-m_{n}+1,n}

and otherwise

up,nuq,n=0.subscript𝑢𝑝𝑛subscript𝑢𝑞𝑛0u_{p,n}\ast u_{q,n}=0.

In the following lemma we give the coefficient functionals in the boundary condition.

Lemma 4.2 The coefficient functionals in the projector expansion Pnf=k=0mn1Cmn1k,n(f)uk,nsubscript𝑃𝑛𝑓superscriptsubscript𝑘0subscript𝑚𝑛1subscript𝐶subscript𝑚𝑛1𝑘𝑛𝑓subscript𝑢𝑘𝑛P_{n}f=\sum_{k=0}^{m_{n}-1}C_{m_{n}-1-k,n}(f)u_{k,n} in the root subspace Ker(LλnI)mn𝐾𝑒𝑟superscript𝐿subscript𝜆𝑛𝐼subscript𝑚𝑛Ker(L-\lambda_{n}I)^{m_{n}} are of the form

Ck,n(f)=iUμ{0μf(ξ)(i(μξ))kk!exp(iλn(μξ))𝑑ξ},0kmn1.formulae-sequencesubscript𝐶𝑘𝑛𝑓𝑖subscript𝑈𝜇superscriptsubscript0𝜇𝑓𝜉superscript𝑖𝜇𝜉𝑘𝑘𝑒𝑥𝑝𝑖subscript𝜆𝑛𝜇𝜉differential-d𝜉0𝑘subscript𝑚𝑛1C_{k,n}(f)=-iU_{\mu}\{\int_{0}^{\mu}f(\xi)\frac{(i(\mu-\xi))^{k}}{k!}exp(i\lambda_{n}(\mu-\xi))d\xi\},0\leq k\leq m_{n}-1.

Proof. By the definition we have Pnf=fumn1,nsubscript𝑃𝑛𝑓𝑓subscript𝑢subscript𝑚𝑛1𝑛P_{n}f=f\ast u_{m_{n}-1,n}, but on other hand Pnf=Cmn1,n(f)u0,n+Cmn2,n(f)u1,n++C0,n(f)umn1,n.subscript𝑃𝑛𝑓subscript𝐶subscript𝑚𝑛1𝑛𝑓subscript𝑢0𝑛subscript𝐶subscript𝑚𝑛2𝑛𝑓subscript𝑢1𝑛subscript𝐶0𝑛𝑓subscript𝑢subscript𝑚𝑛1𝑛P_{n}f=C_{m_{n}-1,n}(f)u_{0,n}+C_{m_{n}-2,n}(f)u_{1,n}+...+C_{0,n}(f)u_{m_{n}-1,n}. Then we get the equality

fumn1,n=k=0mn1Cmn1k,n(f)uk,n,𝑓subscript𝑢subscript𝑚𝑛1𝑛superscriptsubscript𝑘0subscript𝑚𝑛1subscript𝐶subscript𝑚𝑛1𝑘𝑛𝑓subscript𝑢𝑘𝑛f\ast u_{m_{n}-1,n}=\sum_{k=0}^{m_{n}-1}C_{m_{n}-1-k,n}(f)u_{k,n}, (15)

As for u0,nsubscript𝑢0𝑛u_{0,n}, we have

fumn1,nu0,n=k=0mn1Cmn1k,n(f)uk,nu0,n,𝑓subscript𝑢subscript𝑚𝑛1𝑛subscript𝑢0𝑛superscriptsubscript𝑘0subscript𝑚𝑛1subscript𝐶subscript𝑚𝑛1𝑘𝑛𝑓subscript𝑢𝑘𝑛subscript𝑢0𝑛f\ast u_{m_{n}-1,n}\ast u_{0,n}=\sum_{k=0}^{m_{n}-1}C_{m_{n}-1-k,n}(f)u_{k,n}\ast u_{0,n},

then by using Lemma 3.1, we get

fu0,n=C0,n(f)u0,n.𝑓subscript𝑢0𝑛subscript𝐶0𝑛𝑓subscript𝑢0𝑛f\ast u_{0,n}=C_{0,n}(f)u_{0,n}. (16)

Let rewrite the left side of  (16) by using formula  (4)

fu0,n=iUμ{μxf(ξ)u0,n(x+μξ)𝑑ξ}=𝑓subscript𝑢0𝑛𝑖subscript𝑈𝜇superscriptsubscript𝜇𝑥𝑓𝜉subscript𝑢0𝑛𝑥𝜇𝜉differential-d𝜉absentf\ast u_{0,n}=-iU_{\mu}\{\int_{\mu}^{x}f(\xi)u_{0,n}(x+\mu-\xi)d\xi\}=
=iUμ{0xf(ξ)u0,n(x+μξ)𝑑ξ}iUμ{0μf(ξ)u0,n(x+μξ)𝑑ξ}.absent𝑖subscript𝑈𝜇superscriptsubscript0𝑥𝑓𝜉subscript𝑢0𝑛𝑥𝜇𝜉differential-d𝜉𝑖subscript𝑈𝜇superscriptsubscript0𝜇𝑓𝜉subscript𝑢0𝑛𝑥𝜇𝜉differential-d𝜉=-iU_{\mu}\{\int_{0}^{x}f(\xi)u_{0,n}(x+\mu-\xi)d\xi\}-iU_{\mu}\{\int_{0}^{\mu}f(\xi)u_{0,n}(x+\mu-\xi)d\xi\}.

Since iUμ{0xf(ξ)d0,nexp(iλn(x+μξ))𝑑ξ}=𝑖subscript𝑈𝜇superscriptsubscript0𝑥𝑓𝜉subscript𝑑0𝑛𝑒𝑥𝑝𝑖subscript𝜆𝑛𝑥𝜇𝜉differential-d𝜉absentiU_{\mu}\{\int_{0}^{x}f(\xi)d_{0,n}exp(i\lambda_{n}(x+\mu-\xi))d\xi\}=

=d0,nexp(iλx)i0xf(ξ)exp(iλnξ)𝑑ξ[1λn0bexp(iλnμ)σ(μ)¯𝑑μ]=absentsubscript𝑑0𝑛𝑒𝑥𝑝𝑖𝜆𝑥𝑖superscriptsubscript0𝑥𝑓𝜉𝑒𝑥𝑝𝑖subscript𝜆𝑛𝜉differential-d𝜉delimited-[]1subscript𝜆𝑛superscriptsubscript0𝑏𝑒𝑥𝑝𝑖subscript𝜆𝑛𝜇¯𝜎𝜇differential-d𝜇absent=d_{0,n}exp(i\lambda x)i\int_{0}^{x}f(\xi)exp(-i\lambda_{n}\xi)d\xi[1-\lambda_{n}\int_{0}^{b}exp(i\lambda_{n}\mu)\overline{\sigma(\mu)}d\mu]=
=u0,niΔ(λn)0xf(ξ)exp(iλnξ)𝑑ξ,absentsubscript𝑢0𝑛𝑖Δsubscript𝜆𝑛superscriptsubscript0𝑥𝑓𝜉𝑒𝑥𝑝𝑖subscript𝜆𝑛𝜉differential-d𝜉=u_{0,n}i\Delta(\lambda_{n})\int_{0}^{x}f(\xi)exp(-i\lambda_{n}\xi)d\xi,

the first term is equal to zero. And

fu0,n=iUμ{0μf(ξ)u0,n(x+μξ)𝑑ξ}=iUμ{0μf(ξ)d0,nexp(iλn(x+μξ))𝑑ξ}=𝑓subscript𝑢0𝑛𝑖subscript𝑈𝜇superscriptsubscript0𝜇𝑓𝜉subscript𝑢0𝑛𝑥𝜇𝜉differential-d𝜉𝑖subscript𝑈𝜇superscriptsubscript0𝜇𝑓𝜉subscript𝑑0𝑛𝑒𝑥𝑝𝑖subscript𝜆𝑛𝑥𝜇𝜉differential-d𝜉absentf\ast u_{0,n}=-iU_{\mu}\{\int_{0}^{\mu}f(\xi)u_{0,n}(x+\mu-\xi)d\xi\}=-iU_{\mu}\{\int_{0}^{\mu}f(\xi)d_{0,n}exp(i\lambda_{n}(x+\mu-\xi))d\xi\}=
=dn,0exp(iλnξ)iUμ{0μf(ξ)exp(iλn(μξ))𝑑ξ}=iUμ{0μf(ξ)exp(iλn(μξ))𝑑ξ}u0,n.absentsubscript𝑑𝑛0𝑒𝑥𝑝𝑖subscript𝜆𝑛𝜉𝑖subscript𝑈𝜇superscriptsubscript0𝜇𝑓𝜉𝑒𝑥𝑝𝑖subscript𝜆𝑛𝜇𝜉differential-d𝜉𝑖subscript𝑈𝜇superscriptsubscript0𝜇𝑓𝜉𝑒𝑥𝑝𝑖subscript𝜆𝑛𝜇𝜉differential-d𝜉subscript𝑢0𝑛=-d_{n,0}exp(-i\lambda_{n}\xi)iU_{\mu}\{\int_{0}^{\mu}f(\xi)exp(i\lambda_{n}(\mu-\xi))d\xi\}=-iU_{\mu}\{\int_{0}^{\mu}f(\xi)exp(i\lambda_{n}(\mu-\xi))d\xi\}u_{0,n}.

By comparing the right and the left hand side of  (16), we get

C0,n(f)=iUμ{0μf(ξ)exp(iλn(μξ))𝑑ξ}.subscript𝐶0𝑛𝑓𝑖subscript𝑈𝜇superscriptsubscript0𝜇𝑓𝜉𝑒𝑥𝑝𝑖subscript𝜆𝑛𝜇𝜉differential-d𝜉C_{0,n}(f)=-iU_{\mu}\{\int_{0}^{\mu}f(\xi)exp(i\lambda_{n}(\mu-\xi))d\xi\}.

Now suppose that

Ck,n(f)=iUμ{0μf(ξ)(i(μξ))kk!exp(iλn(μξ))𝑑ξ},k=0:s1,1smn1.:formulae-sequencesubscript𝐶𝑘𝑛𝑓𝑖subscript𝑈𝜇superscriptsubscript0𝜇𝑓𝜉superscript𝑖𝜇𝜉𝑘𝑘𝑒𝑥𝑝𝑖subscript𝜆𝑛𝜇𝜉differential-d𝜉𝑘0𝑠11𝑠subscript𝑚𝑛1C_{k,n}(f)=-iU_{\mu}\{\int_{0}^{\mu}f(\xi)\frac{(i(\mu-\xi))^{k}}{k!}exp(i\lambda_{n}(\mu-\xi))d\xi\},k=0:s-1,1\leq s\leq m_{n}-1.

Let us prove that

Cs,n(f)=iUμ{0μf(ξ)(i(μξ))ss!exp(iλn(μξ))𝑑ξ},1smn1.formulae-sequencesubscript𝐶𝑠𝑛𝑓𝑖subscript𝑈𝜇superscriptsubscript0𝜇𝑓𝜉superscript𝑖𝜇𝜉𝑠𝑠𝑒𝑥𝑝𝑖subscript𝜆𝑛𝜇𝜉differential-d𝜉1𝑠subscript𝑚𝑛1C_{s,n}(f)=-iU_{\mu}\{\int_{0}^{\mu}f(\xi)\frac{(i(\mu-\xi))^{s}}{s!}exp(i\lambda_{n}(\mu-\xi))d\xi\},1\leq s\leq m_{n}-1.

By convolving the both sides of  (15) with us,nsubscript𝑢𝑠𝑛u_{s,n}, we have

fumn1,nus,n=k=0mn1Cmn1k,n(f)uk,nus,n.𝑓subscript𝑢subscript𝑚𝑛1𝑛subscript𝑢𝑠𝑛superscriptsubscript𝑘0subscript𝑚𝑛1subscript𝐶subscript𝑚𝑛1𝑘𝑛𝑓subscript𝑢𝑘𝑛subscript𝑢𝑠𝑛f\ast u_{m_{n}-1,n}\ast u_{s,n}=\sum_{k=0}^{m_{n}-1}C_{m_{n}-1-k,n}(f)u_{k,n}\ast u_{s,n}. (17)

The equality  (17) is changed to

fus,n=k=mn1smn1Cmn1k,n(f)uk+smn+1,n.𝑓subscript𝑢𝑠𝑛superscriptsubscript𝑘subscript𝑚𝑛1𝑠subscript𝑚𝑛1subscript𝐶subscript𝑚𝑛1𝑘𝑛𝑓subscript𝑢𝑘𝑠subscript𝑚𝑛1𝑛f\ast u_{s,n}=\sum_{k=m_{n}-1-s}^{m_{n}-1}C_{m_{n}-1-k,n}(f)u_{k+s-m_{n}+1,n}.

Let us related the index k𝑘k by l=mn1k,𝑙subscript𝑚𝑛1𝑘l=m_{n}-1-k, then we get

fus,n=l=0sCl,n(f)us1,n.𝑓subscript𝑢𝑠𝑛superscriptsubscript𝑙0𝑠subscript𝐶𝑙𝑛𝑓subscript𝑢𝑠1𝑛f\ast u_{s,n}=\sum_{l=0}^{s}C_{l,n}(f)u_{s-1,n}. (18)

As in the previous case by using formula  (4), we write

fus,n=iUμ{μxf(ξ)us,n(x+μξ)𝑑ξ}=𝑓subscript𝑢𝑠𝑛𝑖subscript𝑈𝜇superscriptsubscript𝜇𝑥𝑓𝜉subscript𝑢𝑠𝑛𝑥𝜇𝜉differential-d𝜉absentf\ast u_{s,n}=iU_{\mu}\{\int_{\mu}^{x}f(\xi)u_{s,n}(x+\mu-\xi)d\xi\}=
=iUμ{0xf(ξ)us,n(x+μξ)𝑑ξ}iUμ{0μf(ξ)us,n(x+μξ)𝑑ξ}.absent𝑖subscript𝑈𝜇superscriptsubscript0𝑥𝑓𝜉subscript𝑢𝑠𝑛𝑥𝜇𝜉differential-d𝜉𝑖subscript𝑈𝜇superscriptsubscript0𝜇𝑓𝜉subscript𝑢𝑠𝑛𝑥𝜇𝜉differential-d𝜉=iU_{\mu}\{\int_{0}^{x}f(\xi)u_{s,n}(x+\mu-\xi)d\xi\}-iU_{\mu}\{\int_{0}^{\mu}f(\xi)u_{s,n}(x+\mu-\xi)d\xi\}.

Since

iUμ{0xf(ξ)j=0sdj,nj!(i(x+μξ))sj(sj)!exp(iλn(x+μξ))dξ}=𝑖subscript𝑈𝜇superscriptsubscript0𝑥𝑓𝜉superscriptsubscript𝑗0𝑠subscript𝑑𝑗𝑛𝑗superscript𝑖𝑥𝜇𝜉𝑠𝑗𝑠𝑗𝑒𝑥𝑝𝑖subscript𝜆𝑛𝑥𝜇𝜉𝑑𝜉absentiU_{\mu}\{\int_{0}^{x}f(\xi)\sum_{j=0}^{s}\frac{d_{j,n}}{j!}\frac{(i(x+\mu-\xi))^{s-j}}{(s-j)!}exp(i\lambda_{n}(x+\mu-\xi))d\xi\}=
=j=0sdj,nj!exp(iλnx)p=0sj(ix)sjp(sjp)!iUμ{0xf(ξ)(i(μξ))pp!exp(iλn(μξ))𝑑ξ}=absentsuperscriptsubscript𝑗0𝑠subscript𝑑𝑗𝑛𝑗𝑒𝑥𝑝𝑖subscript𝜆𝑛𝑥superscriptsubscript𝑝0𝑠𝑗superscript𝑖𝑥𝑠𝑗𝑝𝑠𝑗𝑝𝑖subscript𝑈𝜇superscriptsubscript0𝑥𝑓𝜉superscript𝑖𝜇𝜉𝑝𝑝𝑒𝑥𝑝𝑖subscript𝜆𝑛𝜇𝜉differential-d𝜉absent=\sum_{j=0}^{s}\frac{d_{j,n}}{j!}exp(i\lambda_{n}x)\sum_{p=0}^{s-j}\frac{(ix)^{s-j-p}}{(s-j-p)!}iU_{\mu}\{\int_{0}^{x}f(\xi)\frac{(i(\mu-\xi))^{p}}{p!}exp(i\lambda_{n}(\mu-\xi))d\xi\}=
=j=0sjλjG(f;x,λ)|λ=λnusj,nabsentevaluated-atsuperscriptsubscript𝑗0𝑠superscript𝑗superscript𝜆𝑗𝐺𝑓𝑥𝜆𝜆subscript𝜆𝑛subscript𝑢𝑠𝑗𝑛=\sum_{j=0}^{s}\frac{\partial^{j}}{\partial\lambda^{j}}G(f;x,\lambda)|_{\lambda=\lambda_{n}}u_{s-j,n}

the first term is equal to zero, here

G(f;x,λ):=iΔ(λ)0xf(ξ)exp(iλξ)𝑑ξ.assign𝐺𝑓𝑥𝜆𝑖Δ𝜆superscriptsubscript0𝑥𝑓𝜉𝑒𝑥𝑝𝑖𝜆𝜉differential-d𝜉G(f;x,\lambda):=i\Delta(\lambda)\int_{0}^{x}f(\xi)exp(-i\lambda\xi)d\xi.

It is obvious that if λnsubscript𝜆𝑛\lambda_{n} is zero of the function Δ(λ)Δ𝜆\Delta(\lambda), then jλjG(f;x,λ)|λ=λn=0,jZ+formulae-sequenceevaluated-atsuperscript𝑗superscript𝜆𝑗𝐺𝑓𝑥𝜆𝜆subscript𝜆𝑛0for-all𝑗subscript𝑍\frac{\partial^{j}}{\partial\lambda^{j}}G(f;x,\lambda)|_{\lambda=\lambda_{n}}=0,\forall j\in Z_{+}.

In the left hand side of  (18), we then have

fus,n=iUμ{0μf(ξ)us,n(x+μξ)𝑑ξ}=𝑓subscript𝑢𝑠𝑛𝑖subscript𝑈𝜇superscriptsubscript0𝜇𝑓𝜉subscript𝑢𝑠𝑛𝑥𝜇𝜉differential-d𝜉absentf\ast u_{s,n}=-iU_{\mu}\{\int_{0}^{\mu}f(\xi)u_{s,n}(x+\mu-\xi)d\xi\}=
=iUμ{0μf(ξ)j=0sdj,nj!(i(x+μξ))sj(sj)!exp(iλn(x+μξ))dξ}=absent𝑖subscript𝑈𝜇superscriptsubscript0𝜇𝑓𝜉superscriptsubscript𝑗0𝑠subscript𝑑𝑗𝑛𝑗superscript𝑖𝑥𝜇𝜉𝑠𝑗𝑠𝑗𝑒𝑥𝑝𝑖subscript𝜆𝑛𝑥𝜇𝜉𝑑𝜉absent=-iU_{\mu}\{\int_{0}^{\mu}f(\xi)\sum_{j=0}^{s}\frac{d_{j,n}}{j!}\frac{(i(x+\mu-\xi))^{s-j}}{(s-j)!}exp(i\lambda_{n}(x+\mu-\xi))d\xi\}=
=j=0sdj,nj!exp(iλnx)p=0sj(ix)sjp(sjp)!iUμ{0μf(ξ)(i(μξ))pp!exp(iλn(μξ))𝑑ξ}=absentsuperscriptsubscript𝑗0𝑠subscript𝑑𝑗𝑛𝑗𝑒𝑥𝑝𝑖subscript𝜆𝑛𝑥superscriptsubscript𝑝0𝑠𝑗superscript𝑖𝑥𝑠𝑗𝑝𝑠𝑗𝑝𝑖subscript𝑈𝜇superscriptsubscript0𝜇𝑓𝜉superscript𝑖𝜇𝜉𝑝𝑝𝑒𝑥𝑝𝑖subscript𝜆𝑛𝜇𝜉differential-d𝜉absent=-\sum_{j=0}^{s}\frac{d_{j,n}}{j!}exp(i\lambda_{n}x)\sum_{p=0}^{s-j}\frac{(ix)^{s-j-p}}{(s-j-p)!}iU_{\mu}\{\int_{0}^{\mu}f(\xi)\frac{(i(\mu-\xi))^{p}}{p!}exp(i\lambda_{n}(\mu-\xi))d\xi\}=
=j=0sCj,n(f)usj,niUμ{0μf(ξ)(i(μξ))ss!exp(iλn(μξ))𝑑ξ}u0,n.absentsuperscriptsubscript𝑗0𝑠subscript𝐶𝑗𝑛𝑓subscript𝑢𝑠𝑗𝑛𝑖subscript𝑈𝜇superscriptsubscript0𝜇𝑓𝜉superscript𝑖𝜇𝜉𝑠𝑠𝑒𝑥𝑝𝑖subscript𝜆𝑛𝜇𝜉differential-d𝜉subscript𝑢0𝑛=\sum_{j=0}^{s}C_{j,n}(f)u_{s-j,n}-iU_{\mu}\{\int_{0}^{\mu}f(\xi)\frac{(i(\mu-\xi))^{s}}{s!}exp(i\lambda_{n}(\mu-\xi))d\xi\}u_{0,n}.

By comparing the right and the left hand sides of the equality  (18), we get

Cs,n(f)=iUμ{0μf(ξ)(i(μξ))ss!exp(iλn(μξ))𝑑ξ}.subscript𝐶𝑠𝑛𝑓𝑖subscript𝑈𝜇superscriptsubscript0𝜇𝑓𝜉superscript𝑖𝜇𝜉𝑠𝑠𝑒𝑥𝑝𝑖subscript𝜆𝑛𝜇𝜉differential-d𝜉C_{s,n}(f)=-iU_{\mu}\{\int_{0}^{\mu}f(\xi)\frac{(i(\mu-\xi))^{s}}{s!}exp(i\lambda_{n}(\mu-\xi))d\xi\}.

Hence we have explicitly constructed a biorthogonal system to the system {uk,n,λnσ(L)}.subscript𝑢𝑘𝑛subscript𝜆𝑛𝜎𝐿\{u_{k,n},\lambda_{n}\in\sigma(L)\}.

Theorem 4.2 The chosen basis system {uk,n,k=0,,mn1,λnσ(L)}formulae-sequencesubscript𝑢𝑘𝑛𝑘0subscript𝑚𝑛1subscript𝜆𝑛𝜎𝐿\{u_{k,n},k=0,...,m_{n}-1,\lambda_{n}\in\sigma(L)\} is minimal in L2(0,b),subscript𝐿20𝑏L_{2}(0,b), i.e. there exists a biorthogonal system of the form

hk,n(ξ)=ξbσ(μ)¯μ((i(μξ))kk!exp(iλn(μξ)))𝑑μ,k=0,,mn1.formulae-sequencesubscript𝑘𝑛𝜉superscriptsubscript𝜉𝑏¯𝜎𝜇𝜇superscript𝑖𝜇𝜉𝑘𝑘𝑒𝑥𝑝𝑖subscript𝜆𝑛𝜇𝜉differential-d𝜇𝑘0subscript𝑚𝑛1h_{k,n}(\xi)=\int_{\xi}^{b}\overline{\sigma(\mu)}\frac{\partial}{\partial\mu}(\frac{(i(\mu-\xi))^{k}}{k!}exp(i\lambda_{n}(\mu-\xi)))d\mu,k=0,...,m_{n}-1.

5. On the Sedletskiy formula for the remainder term

It is well–known that the partial sum of the Fourier series is written in the form

SR(f;x)=12πi|λ|=R(LλI)1f𝑑λ=|λn|<RPλnf.subscript𝑆𝑅𝑓𝑥12𝜋𝑖subscriptcontour-integral𝜆𝑅superscript𝐿𝜆𝐼1𝑓differential-d𝜆subscriptsubscript𝜆𝑛𝑅subscript𝑃subscript𝜆𝑛𝑓S_{R}(f;x)=-\frac{1}{2\pi i}\oint_{|\lambda|=R}(L-\lambda I)^{-1}fd\lambda=\sum_{|\lambda_{n}|<R}P_{\lambda_{n}}f.

By using  (5), we rewrite the partial sum as

SR(f;x)=12πi|λ|=Rexp(iλx)Δ(λ)f(x)𝑑λ.subscript𝑆𝑅𝑓𝑥12𝜋𝑖subscriptcontour-integral𝜆𝑅𝑒𝑥𝑝𝑖𝜆𝑥Δ𝜆𝑓𝑥differential-d𝜆S_{R}(f;x)=-\frac{1}{2\pi i}\oint_{|\lambda|=R}\frac{exp(i\lambda x)}{\Delta(\lambda)}\ast f(x)d\lambda.

In this formula instead of f𝑓f we put the function exp(iμx).𝑒𝑥𝑝𝑖𝜇𝑥exp(i\mu x). Then we have

SR(exp(iμx);x)=12πi|λ|=Rexp(iλx)Δ(λ)exp(iμx)𝑑λ=subscript𝑆𝑅𝑒𝑥𝑝𝑖𝜇𝑥𝑥12𝜋𝑖subscriptcontour-integral𝜆𝑅𝑒𝑥𝑝𝑖𝜆𝑥Δ𝜆𝑒𝑥𝑝𝑖𝜇𝑥differential-d𝜆absentS_{R}(exp(i\mu x);x)=-\frac{1}{2\pi i}\oint_{|\lambda|=R}\frac{exp(i\lambda x)}{\Delta(\lambda)}\ast exp(i\mu x)d\lambda=

|by applying lemma 2.5| ==

=12πi|λ|=Rexp(iλx)Δ(μ)exp(iμx)Δ(λ)Δ(λ)(μλ)𝑑λ=absent12𝜋𝑖subscriptcontour-integral𝜆𝑅𝑒𝑥𝑝𝑖𝜆𝑥Δ𝜇𝑒𝑥𝑝𝑖𝜇𝑥Δ𝜆Δ𝜆𝜇𝜆differential-d𝜆absent=\frac{1}{2\pi i}\oint_{|\lambda|=R}\frac{exp(i\lambda x)\Delta(\mu)-exp(i\mu x)\Delta(\lambda)}{\Delta(\lambda)(\mu-\lambda)}d\lambda=
=Δ(μ)2πi|λ|=Rexp(iλx)Δ(λ)dλμλ+12πi|λ|=Rexp(iμx)λμ𝑑λ=absentΔ𝜇2𝜋𝑖subscriptcontour-integral𝜆𝑅𝑒𝑥𝑝𝑖𝜆𝑥Δ𝜆𝑑𝜆𝜇𝜆12𝜋𝑖subscriptcontour-integral𝜆𝑅𝑒𝑥𝑝𝑖𝜇𝑥𝜆𝜇differential-d𝜆absent=\frac{\Delta(\mu)}{2\pi i}\oint_{|\lambda|=R}\frac{exp(i\lambda x)}{\Delta(\lambda)}\frac{d\lambda}{\mu-\lambda}+\frac{1}{2\pi i}\oint_{|\lambda|=R}\frac{exp(i\mu x)}{\lambda-\mu}d\lambda=

|by using Cauchy formula to the second term| ==

=exp(iμx)+Δ(μ)2πi|λ|=Rexp(iλx)Δ(λ)dλμλ.absent𝑒𝑥𝑝𝑖𝜇𝑥Δ𝜇2𝜋𝑖subscriptcontour-integral𝜆𝑅𝑒𝑥𝑝𝑖𝜆𝑥Δ𝜆𝑑𝜆𝜇𝜆=exp(i\mu x)+\frac{\Delta(\mu)}{2\pi i}\oint_{|\lambda|=R}\frac{exp(i\lambda x)}{\Delta(\lambda)}\frac{d\lambda}{\mu-\lambda}.

Hence it follows that the formula for the remainder term for f(x)=exp(iμx)𝑓𝑥𝑒𝑥𝑝𝑖𝜇𝑥f(x)=exp(i\mu x) is

QR(exp(iμx);x):=SR(exp(iμx);x)exp(iμx)=Δ(μ)2πi|λ|=Rexp(iλx)Δ(λ)dλμλ,assignsubscript𝑄𝑅𝑒𝑥𝑝𝑖𝜇𝑥𝑥subscript𝑆𝑅𝑒𝑥𝑝𝑖𝜇𝑥𝑥𝑒𝑥𝑝𝑖𝜇𝑥Δ𝜇2𝜋𝑖subscriptcontour-integral𝜆𝑅𝑒𝑥𝑝𝑖𝜆𝑥Δ𝜆𝑑𝜆𝜇𝜆Q_{R}(exp(i\mu x);x):=S_{R}(exp(i\mu x);x)-exp(i\mu x)=\frac{\Delta(\mu)}{2\pi i}\oint_{|\lambda|=R}\frac{exp(i\lambda x)}{\Delta(\lambda)}\frac{d\lambda}{\mu-\lambda}, (19)

which is valid for any μ𝜇\mu. Since an arbitrary element f𝑓f of the space L2(0,b)subscript𝐿20𝑏L_{2}(0,b) is represented in the form

f(x)=12πf^(μ)exp(iμx)𝑑μ,𝑓𝑥12𝜋superscriptsubscript^𝑓𝜇𝑒𝑥𝑝𝑖𝜇𝑥differential-d𝜇f(x)=\frac{1}{2\pi}\int_{-\infty}^{\infty}\hat{f}(-\mu)exp(i\mu x)d\mu,

where f^(μ)^𝑓𝜇\widehat{f}(\mu) is the Fourier transform of the function f(x),𝑓𝑥f(x), from  (19), we obtain the integral form of the remainder term for an arbitrary function f(x)𝑓𝑥f(x) in the space L2(0,b),subscript𝐿20𝑏L_{2}(0,b),

QR(f;x):=SR(f(x);x)f(x)=12πi|λ|=Rexp(iλx)Δ(λ)𝑑λ(12πf^(μ)Δ(μ)μλ𝑑μ).assignsubscript𝑄𝑅𝑓𝑥subscript𝑆𝑅𝑓𝑥𝑥𝑓𝑥12𝜋𝑖subscriptcontour-integral𝜆𝑅𝑒𝑥𝑝𝑖𝜆𝑥Δ𝜆differential-d𝜆12𝜋superscriptsubscript^𝑓𝜇Δ𝜇𝜇𝜆differential-d𝜇Q_{R}(f;x):=S_{R}(f(x);x)-f(x)=\frac{1}{2\pi i}\oint_{|\lambda|=R}\frac{exp(i\lambda x)}{\Delta(\lambda)}d\lambda(\frac{1}{2\pi}\int_{-\infty}^{\infty}\frac{\hat{f}(-\mu)\Delta(\mu)}{\mu-\lambda}d\mu).

A similar formula was proved in another way by A.M. Sedletskiy in the work [6]. Let us write the set of conditions

{maxsuppσ(x)=b,minsupp(σ(x)+i)=0,cases𝑠𝑢𝑝𝑝𝜎𝑥𝑏missing-subexpression𝑠𝑢𝑝𝑝𝜎𝑥𝑖0missing-subexpression\left\{\begin{array}[]{ll}\max supp\sigma(x)=b,&\\ \min supp(\sigma(x)+i)=0,&\\ \end{array}\right. (A)𝐴
sup|Imλn|=M<,supremum𝐼𝑚subscript𝜆𝑛𝑀\sup|Im\lambda_{n}|=M<\infty, (B)𝐵
infnk|λnλk|>0,subscriptinfimum𝑛𝑘subscript𝜆𝑛subscript𝜆𝑘0\inf_{n\neq k}|\lambda_{n}-\lambda_{k}|>0, (C)𝐶
supmn=m<.supremumsubscript𝑚𝑛𝑚\sup m_{n}=m<\infty. (D)𝐷

Denote ω(λ)=|Δ(λ)|2𝜔𝜆superscriptΔ𝜆2\omega(\lambda)=|\Delta(\lambda)|^{2}. Let us write the Muckenhoupt condition

supl(1|I|Iω(λ)𝑑λ)(1|I|Iω1(λ)𝑑λ)<,subscriptsupremum𝑙1𝐼subscript𝐼𝜔𝜆differential-d𝜆1𝐼subscript𝐼superscript𝜔1𝜆differential-d𝜆\sup_{l}(\frac{1}{|I|}\int_{I}\omega(\lambda)d\lambda)(\frac{1}{|I|}\int_{I}\omega^{-1}(\lambda)d\lambda)<\infty, (E)𝐸

where I𝐼I an arbitrary interval of the real axis. If the operator

S+:λnΛPn(x)exp(iλnx)Reλn>0Pn(x)exp(iλnx):superscript𝑆maps-tosubscriptsubscript𝜆𝑛Λsubscript𝑃𝑛𝑥𝑒𝑥𝑝𝑖subscript𝜆𝑛𝑥subscript𝑅𝑒subscript𝜆𝑛0subscript𝑃𝑛𝑥𝑒𝑥𝑝𝑖subscript𝜆𝑛𝑥S^{+}:\sum_{\lambda_{n}\in\Lambda}P_{n}(x)exp(i\lambda_{n}x)\mapsto\sum_{Re\lambda_{n}>0}P_{n}(x)exp(i\lambda_{n}x)

is bounded in the space L2(0,b)subscript𝐿20𝑏L_{2}(0,b), then we will say that the basis {uk,n,k=0,,mn1,λnσ(L)}formulae-sequencesubscript𝑢𝑘𝑛𝑘0subscript𝑚𝑛1subscript𝜆𝑛𝜎𝐿\{u_{k,n},k=0,...,m_{n}-1,\lambda_{n}\in\sigma(L)\} of the space L2(0,b)subscript𝐿20𝑏L_{2}(0,b) is Riesz basis.

The following theorems are true.

Theorem 5.1 Let the conditions (A), (B), (C), (D) be valid and assume that the function ω(λ)=|Δ(λ)|2𝜔𝜆superscriptΔ𝜆2\omega(\lambda)=|\Delta(\lambda)|^{2} satisfies the Muckenhoupt condition (E). Then the system {uk,n,k=0,,mn1,λnσ(L)}formulae-sequencesubscript𝑢𝑘𝑛𝑘0subscript𝑚𝑛1subscript𝜆𝑛𝜎𝐿\{u_{k,n},k=0,...,m_{n}-1,\lambda_{n}\in\sigma(L)\} is a Riesz basis in the space L2(0,b)subscript𝐿20𝑏L_{2}(0,b).

Theorem 5.2 Assume the conditions of Theorem 5.1, except, perhaps, the condition (D). Then for every fL2(0,b)𝑓subscript𝐿20𝑏f\in L_{2}(0,b), we have

x12(bx)12Qr(f,x)C[0,b]0subscriptnormsuperscript𝑥12superscript𝑏𝑥12subscript𝑄𝑟𝑓𝑥𝐶0𝑏0\|x^{\frac{1}{2}}(b-x)^{\frac{1}{2}}Q_{r}(f,x)\|_{C[0,b]}\rightarrow 0

continuously for r𝑟r\rightarrow\infty.

Theorem 5.3 Suppose the conditions of Theorem 5.1. Then for every fL2(0,b)𝑓subscript𝐿20𝑏f\in L_{2}(0,b) the coefficient sequence satisfies

{{ck,n}k=0}n=0l2,superscriptsubscriptsuperscriptsubscriptsubscript𝑐𝑘𝑛𝑘0𝑛0subscript𝑙2\{\{c_{k,n}\}_{k=0}^{\infty}\}_{n=0}^{\infty}\in l_{2},

and {ck,n}l2C(L)fL2.subscriptnormsubscript𝑐𝑘𝑛subscript𝑙2𝐶𝐿subscriptnorm𝑓subscript𝐿2\|\{c_{k,n}\}\|_{l_{2}}\leq C(L)\|f\|_{L_{2}}.

REFERENCE

[1] M.A. Naimark, Linear differential operators, GITTL, Moscow, 1954; English transl., Part II, Ungar, New York, 1968.

[2] M. Ruzhansky, V. Turunen, Pseudo-Differential Operators and Symmetries, Birkhauser, 2010.

[3] B.E. Kanguzhin and M.A. Sadybekov, Differential operators on a segment. Distributions of the eigenvalues, Gylym, Almaty, 1996. [in russian].

[4] E.C. Titchmarsh, The zeros of certain integral functions // Proc. London Math. Soc. 1926, V. 25, No 4, pp. 283–302.

[5] M.L. Cartwright, The zeros of certain integral functions // The Quarterly Journal of Math., Oxford series, 1930, V. 1, No 1, pp. 38–59.

[6] A.M. Sedletskiy, On biortogonal expansions of functions to exponent series on a real segment // Usp. Mat. Nauk, 1982, V. 37, No 5(227), pp. 51–95 [in russian].